10 Years of the Palliative Medicine Working Group in the Network of Top Oncology Centers - Berendt, Julia; Gahr, Susanne; Heckel, Maria; Tewes, Mitra; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2022)
CRIS-Team WoS Importer:2022-01-14

A Lightweight Robust Approach for Automatic Heart Murmurs and Clinical Outcomes Classification from Phonocardiogram Recordings - Lu, Hui; Yip, Julia; Steigleder, Tobias; Grießhammer, Stefan; Heckel, Maria; Jami, Jitin; Eskofier, Björn; Ostgathe, Christoph; Kölpin, Alexander (2022 Computing in Cardiology (CinC), 2022)
Cardiac auscultation provides an efficient and costeffective way for cardiac disease pre-screening. The George B. Moody PhysioNet Challenge 2022 aimed to detect heart murmurs and clinical outcomes with heart sound recordings from multiple auscultation locations. Our team HearHeart proposed a lightweight convolutional neural network (CNN) to detect heart murmurs and a random forest model to classify clinical outcomes. 128 Melspectrogram features and wide features like the sociodemographic data and statistical features are extracted. Different techniques are employed to migrate the data imbalance and model the overfitting problem. We used two data augmentation methods, noise injection and spectrogram augmentation in time and frequency domain to increase the training samples and avoid overfitting during training. Besides, weighted loss functions are applied to both tasks to deal with data imbalance. In the end, we ensembled the models from cross-validation and used voting for the final classification. We achieved a murmur score of 0.791, and a clinical outcome score of 11731.64 on 5-fold cross-validation in the hidden validation set. While on the hidden test set, we achieved a murmur score of 0.780, and a clinical outcome score of 12110, placing our team 1st and 10th in the challenge tasks, respectivel
Keywords: Heart; Training; Frequency-domain analysis; Feature extraction; Data models; Recording; Convolutional neural networks

A Linguistic Model of Communication Types in Palliative Medicine: Effects of Multidrug-Resistant Organisms (MDRO) Colonization or Infection and Isolation Measures in End of Life on Family Caregivers’ Knowledge, Attitude and Practices. - Peters, Joachim; Dykes, Nathan; Heckel, Maria; Ostgathe, Christoph; Habermann, Mechthild (Journal of Palliative Medicine, 2019)

'. . . and then no more kisses!' Exploring patients' experiences on multidrug-resistant bacterial microorganisms and hygiene measures in end-of-life care A mixed-methods study - Heckel, Maria; Sturm, Alexander; Stiel, Stephanie; Ostgathe, Christoph; Herbst, Franziska A.; Tiedtke, Johanna; Adelhardt, Thomas; Reichert, Karen; Sieber, Cornel (Palliative Medicine, 2019)
BACKGROUND: In end-of-life care hygiene, measures concerning multidrug-resistant bacterial microorganisms may contradict the palliative care approach of social inclusion and be burdensome for patients. OBJECTIVES: To integrate patients' perspectives on handling multidrug-resistant bacterial microorganisms at their end of life, their quality of life, the impact of positive multidrug-resistant bacterial microorganisms' diagnosis, protection and isolation measures on their well-being and patients' wishes and needs regarding their care. DESIGN: A mixed-methods convergent parallel design embedded quantitative data on the patients' multidrug-resistant bacterial microorganisms' trajectory and quality of life assessed by the Schedule for the Evaluation of Individual Quality of Life in qualitative data collection via interviews and focus groups. Data analysis was performed according to Grounded Theory and qualitative and quantitative results were interrelated. SETTING/PARTICIPANTS: Between March 2014 and September 2015 at two hospitals adult patients diagnosed with multidrug-resistant bacterial microorganisms and treated in a palliative care department or a geriatric ward were included in the sample group. RESULTS: Patients in end-of-life and geriatric care reported emotional and social impact through multidrug-resistant bacterial microorganisms' diagnosis itself, hygiene measures and lack of information. This impact affects aspects relevant to the patients' quality of life. Patients' wishes for comprehensive communication/information and reduction of social strain were identified from the focus group discussion. CONCLUSION: Patients would benefit from comprehensible information on multidrug-resistant bacterial microorganisms. Strategies minimizing social exclusion and emotional impact of multidrug-resistant bacterial microorganisms' diagnosis in end-of-life care are needed as well as adaption or supplementation of standard multidrug-resistant bacterial microorganisms' policies of hospitals.
EVALuna2:204831

Are There Entity-Specific Criteria for Initiation of Specialized Palliative Care for Incurable Cancer? A Scoping Review - Gahr, Susanne; Brunner, Sarah; Heckel, Maria; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2023)
Background/Objective Finding the right time for offering specialized palliative care to patients with incurable cancer remains challenging. The aim of the scoping review was to identify appropriate entity-specific criteria. Method A scoping review was conducted in the online databases PubMed and Scopus in February 2020. The aim of the literature search was to identify original English- and German-language papers published between 2009 and February 2020 providing evidence on which entity-specific and entity-independent criteria of non- curable cancers are used to integrate affected patients into specialized palliative care in a timely manner. A total of 13 relevant articles were identified. In accordance with the method of the scoping review, a formal assessment of the methodological quality of the included literature was not performed. Results The relevant publications included six reviews and seven original articles. None of the publications analysed explicitly cited characteristic criteria related to specific cancer entities. Incurability/advanced tumour disease, quality of life, distressing symptoms, ECOG status, psychosocial needs, comorbidities, tumour-associated complications, treatment decision/ no treatment options, and limited lifetime prognosis were used or suggested as criteria for integration into specialized palliative care independently of cancer entity. Tools were used to elicit the criteria. No specific characteristic scores were specified for the tools that could detect an expression of the criteria relevant for integration into specialized palliative care. Conclusion To determine the moment of timely integration of specialized palliative care for non-curable cancers, there are no entity-specific criteria and parameters to date. However, it can be deduced from the analysis that all patients with a non-curable or advanced cancer suffering from a reduction/loss of their quality of life and a complex symptom burden, especially depression and pain, should receive the offer of specialized palliative care, irrespective of their entity. Defining criteria in general as characteristic values and consecutively defining a measured value or cutoff value could be a possibility to facilitate a timely integration of palliative care via e. g., a scoring system. So far, it is unclear which combinations of survey instruments or screening tools could serve to capture timely integration.
CRIS-Team WoS Importer:2023-05-05

Assessment of the quality of end-of-life care: translation and validation of the German version of the "Care of the Dying Evaluation" (CODE-GER) - a questionnaire for bereaved relatives - Vogt, Annika; Stiel, Stephanie; Heckel, Maria; Goebel, Swantje; Mai, Sandra Stephanie; Seifert, Andreas; Gerlach, Christina; Ostgathe, Christoph; Weber, Martin (Health and Quality of Life Outcomes, 2020)
BACKGROUND: International studies indicate deficits in end-of-life care that can lead to distress for patients and their next-of-kin. The aim of the study was to translate and validate the "Care of the Dying Evaluation" (CODE) into German (CODE-GER). METHODS: Translation according to EORTC (European Organisation for Research and Treatment of Cancer) guidelines was followed by data collection to evaluate psychometric properties of CODE-GER. Participants were next-of-kin of patients who had died an expected death in two hospitals. They were invited to participate at least eight, but not later than 16 weeks after the patient's death. To calculate construct validity, the Palliative care Outcome Scale (POS) was assessed. Difficulty and perceived strain of answering the questionnaire were assessed by a numeric scale (0-10). RESULTS: Out of 1137 next-of-kin eligible, 317 completed the questionnaire (response rate: 27.9%). Data from 237 main sample participants, 38 interraters and 55 next-of-kin who participated for repeated measurement were analysed. Overall internal consistency, α = 0.86, interrater reliability, ICC (1) = 0.79, and retest-reliability, ICC (1, 2) = 0.85, were good. Convergent validity between POS and CODE-GER, r = -.46, was satisfactory. A principal component analysis with varimax rotation showed a 7-factor solution. Difficulty, M = 2.2; SD ± 2.4, and perceived strain, M = 4.1; SD ± 3.0, of completing the questionnaire were rather low. CONCLUSION: The results from the present study confirm CODE-GER as a reliable and valid instrument to assess the quality of care of the dying person. More over our study adds value to the original questionnaire by proposing a deepened analysis of obtained data. The development of seven subscales increases its potential for further surveys and research. TRIAL REGISTRATION: This study was registered retrospectively on the 25th of January 2018 at the German Clinical Trials Register ( DRKS00013916 ).
CRIS-Team Scopus Importer:2020-10-09
Keywords: Hospital; Proxy; Quality of health care; Terminal care; Validation studies; outcome assessment

Care trajectories and survival after discharge from specialized inpatient palliative care-results from an observational follow-up study - Kötzsch, Franziska; Stiel, Stephanie; Heckel, Maria; Ostgathe, Christoph; Klein, Carsten (Supportive Care in Cancer, 2014)
Background Little is known about the patients' individual care trajectories after discharge or transfer from inpatient palliative care units (PCU) to other care settings. This study aims to survey the further care trajectory and overall survival from the time of discharge of patients in a palliative care situation. Patient groups from either the PCU or the palliative care mobile support team (PCMT) are compared in order to analyze the demographic data, discharge settings, frequency of changes of care settings, overall survival from the time of discharge and place of death. Methods In a mono-centre prospective observational study, patients discharged or transferred from a German inpatient PCU or from other hospital wards with support of the PCMT were invited to participate in this study. After discharge, the central care provider, such as inpatient hospices, nursing homes or general practitioners, was asked for information on the care trajectory and on readmissions to hospital in four weekly follow-up phone calls until the patients' death. Place of death and overall survival from the time of discharge were noted. Results During the study period, 467 inpatients from the PCU and 554 inpatients from the PCMT were treated. Ultimately, 418 were discharged. Two hundred forty-five patients agreed to participate in the study, and the majority of them were either discharged home (60.8 %), to inpatient hospices (20.0 %) or to nursing homes (11.0 %). More than half of all of them (55.9 %) stayed continuously in their discharge setting. The remaining 44.1 % experienced a mean number of 3.1 ± 4.1 changes of care setting. Most frequently, patients changed their care setting from private home to hospital (N = 110; 32.4 %) and from hospital back to private home (N = 82; 24.4 %). Patients' mean overall survival from the time of discharge was 51.7 days (median 24.0 days, range 1-488 days). Most patients died in their private home (35.9 %), inpatient hospices (23.3 %) or inpatient PCUs (22.4 %). Conclusions The results show a high percentage of stable care trajectories at the end of life with few or no changes of care setting. To achieve this, well-considered discharge planning and an adequately chosen network of care providers are necessary. © 2014 Springer-Verlag Berlin Heidelberg.
Keywords: Care setting; Disease trajectory; Palliative care; Palliative care mobile support team; Treatment intensity

Caring for patients with brain tumors compared to patients with non-brain tumors Experiences and needs of informal caregivers in home care settings - Heckel, Maria; Hoser, Bettina; Stiel, Stephanie (Journal of Psychosocial Oncology, 2017)
Informal caregivers of patients with advanced cancer experience a challenging time, especially while caring for the patient at home. Aim of this study is to compare experiences, perceived burdens, and needs during home care of informal caregivers of brain tumor patients and informal caregivers of non-brain tumor patients.28 informal caregivers (17 brain tumor group, 11 non-brain tumor group) participated in this study. Semi-structured interviews were conducted to gather information retrospectively. Data was analyzed using principles of thematic analysis method.The results support existing evidence that the themes assessment of the situation, dealing with the situation, effects of the situation, and support by others are of importance to all informal caregivers. Caregivers in the brain tumor group put more emphasis on information and perception of the situation by others than caregivers in the non-brain tumor group.The emerging need for information of caregivers and the effects for caregivers of changes in the perception of the situation by others should be addressed to better support informal caregivers of brain tumor patients.
EVALuna2:26214

Comparison of Patients and their Care in Urban and Rural Specialised Palliative Home Care - A Single Service Analysis - Heckel, Maria; Stiel, Stephanie; Frauendorf, Tobias; Hanke, R. M.; Ostgathe, Christoph (Gesundheitswesen, 2016)
Specialised outpatient palliative care teams (in Germany called SAPV) aim to ensure best possible end-of-life care for outpatients with complex needs. Information on the influence of living areas (rural vs. urban) on patient and care related aspects is rare. This study aims to explore differences between palliative care patients in urban and rural dwellings concerning their nursing and service characteristics.A retrospective data analysis of documentary data for 502 patients supplied by SAPV team from December 2009 to June 2012 was conducted. Patients and care characteristics were investigated by frequency analysis and were compared for both groups of urban and rural dwelling patients (T test, Chi², Fisher's exact test p < 0.05).387 complete data sets could be included. Urban (n=197) and rural (n=190) dwelling patients were almost equally sized groups. The mean age of the whole sample was 74.5 years, 55.3% were female. Most patients were diagnosed with cancer (76.8%). No significant differences in urban and rural dwelling patients concerning most demographics, care, disease and service related aspects of palliative home care could be detected. An exception is that the rate of re-admittance to hospital is higher for rural dwelling patients (Fisher's exact test p=0.022).Although predominantly presumed, the single service analysis shows - except for the re-admittance rate to hospital - no considerable differences between palliative care patients regarding their living area. Our findings indicate that patients cared for in rural and urban settings have similar needs and impose similar requirements on palliative care teams.
EVALuna2:26206

Comparison of terminally ill cancer-vs. non-cancer patients in specialized palliative home care in Germany-A single service analysis - Stiel, Stephanie; Heckel, Maria; Seifert, Andreas; Frauendorf, Tobias; Roland, Hanke; Ostgathe, Christoph (BMC Palliative Care, 2015)
Background: Palliative care (PC) is no longer offered with preference to cancer patients (CA), but also to patients with non-malignant, progressive diseases. Taking current death statistics into account, PC in Europe will face a growing number of patients dying from non-cancer diseases (NCA). More insights into specialized palliative home care (SPHC) in NCAs are needed. Methods: Retrospective analysis and group comparisons between CAs and NCAs of anonymous data of all patients cared for between December 2009 and June 2012 by one SPHC team in Germany. Patient-, disease-and care-related data are documented in clinical routine by specialized PC physicians and nurses in the Information System Palliative Care 3.0 ® (ISPC®). Results: Overall, 502 patients were cared for by the SPHC team; from 387 patients comprehensive data sets were documented. These 387 data sets (CA: N∈=∈300, 77.5 % and NCA: N∈=∈87, 22.5 %) are used for further analysis here. NCAs were significantly older (81 vs. 73 years; p∈<∈.001), than CAs and most often suffered from diseases of the nervous system (40 %). They needed significantly more assistance with defecation (87 vs. 74 %; p∈<∈.001) and urination (47 vs. 29 %; p∈<∈.001) and were more often affected from impaired vigilance (30 vs. 11 %; p∈<∈.001) than CAs. A by trend higher proportion of NCAs died within one day after admission to palliative home care (12 vs. 5 %; p∈<∈.05) and a smaller proportion was re-admitted to hospital during home care (6 vs. 20 %; p∈<∈.001). NCAs died predominantly in nursing homes (50 vs. 20 %; p∈<∈.001). Conclusions: Although the proportion of NCAs was relatively high in this study, the access to PC services seems to takes place late in the disease trajectory, as demonstrated by the lower survival rate for NCAs. Nevertheless, the results show, that NCAs PC needs are as complex and intense as in CAs.
Keywords: Home care; Non-cancer; Non-malignant; Palliative care; Spezialisierte ambulante palliativversorgung

Contactless radar-based heart rate estimation in palliative care – a feasibility study and possible use in symptom management - Grießhammer, Stefan; Malessa, Anke; Lu, Hui; Yip, Julia; Leuschner, Julie; Christgau, Florian; Albrecht, Nils C.; Oesten, Marie; Tran, Thanh Truc; Richer, Robert; Heckel, Maria; Eskofier, Björn; et al. (BMC Palliative Care, 2024)
Background Heart rate (HR) monitoring is a medical standard to provide information about a patient’s health status. In palliative care, relationship and social engagement are crucial therapeutic concepts. For fear of disrupting communication, social contact, and care, continuous HR monitoring is underutilised despite its potential to inform on symptom burden and therapeutic effects. This study investigates radar-based HR monitoring as an innovative and burden-free approach for palliative care patients, compares its accuracy with conventional ECG methods, and shows potential for therapeutic guidance. Methods A single-centre, comparative clinical trial was conducted with palliative care patients at the ward of the Department of Palliative Medicine of the University Hospital of Erlangen. The HR measurements obtained with radar were compared with Holter ECG (study arm I, overnight) and Task Force® Monitor (TFM)-based ECG validation recordings (study arm II, one hour). In addition, long-term radar measurements without validation were analysed in comparison with clinical health records (study arm III). Results Both validation methods showed correlation by scatter plot, modified Bland-Altman plot, and equivalence testing. N = 34 patients participated in study arm I. HR of 4,079 five-minute intervals was analysed. Radar measurements and ECG showed high agreement: difference of HRs was within 5 bpm in 3780 of 4079 (92.67%) and within ±13.4 bpm ( 1.96 times the SD of the mean) in 3979 (97.55%) intervals, respectively. In study arm II, n = 19 patients participated. 57,048 heart beats were analysed. The HR difference was within 5 bpm for 53,583 out of 57,048 beats (93.93%) and within 8.2 bpm ( ± 1.96 times the SD of the mean) in 55,439 beats (97.25%), respectively. Arm III showed HR changes extracted from radar data in correlation with symptoms and treatment. Conclusion Radar-based HR monitoring shows a high agreement in comparison with ECG-based HR monitoring and thus offers an option for continuous and above all burden-free HR assessment, with the potential for use in symptom management in palliative care, among others. Further research and technological advancements are still necessary to fully realize this innovative approach in enhancing palliative care practice

Correction: Possible age-related differences in healthcare professionals’ perspectives on younger and older patients’ autonomy and decision-making in the context of sedation in specialised palliative care: exploratory secondary qualitative content and linguistic conversation analysis of interviews with healthcare professionals (BMC Palliative Care, (2022), 21, 1, (71), 10.1186/s12904-022-00963-y) - Kurkowski, Sandra; Heckel, Maria; Pfaller, Larissa; Peters, Joachim; Bazata, Jeremias; Schildmann, Eva; Ostgathe, Christoph (BMC Palliative Care, 2022)
Following the publication of the original article [1], the author reported that the given name and family name of all authors were erroneously transposed. The author group has been updated above and the original article [1] has been corrected.
CRIS-Team Scopus Importer:2022-09-09

Correction to: Contactless radar-based heart rate estimation in palliative care – a feasibility study and possible use in symptom management (BMC Palliative Care, (2024), 23, 1, (273), 10.1186/s12904-024-01592-3) - Grießhammer, Stefan G.; Malessa, Anke; Lu, Hui; Yip, Julia; Leuschner, Julie; Christgau, Florian; Albrecht, Nils C.; Oesten, Marie; Truc Tran, Thanh; Richer, Robert; Heckel, Maria; Eskofier, Björn; et al. (BMC Palliative Care, 2025)
Correction: BMC Palliat Care 23, 273 (2024). Following publication of the original article [1], the author reported that in the Abstract, Result section, the sentence: “The HR difference was within +/-5 bpm for 53,583 out of 57,048 beats (93.93%) and within +/-8.2 bpm (± 1.96 times the SD of the mean) in 55,439 beats (97.25%), respectively.” Should be. “The HR difference was within +/-5 bpm for 53,583 out of 57,048 beats (93.93%) and within +/-8.2 bpm (± 1.96 times the SD of the mean) in 55,439 beats (97.18%), respectively.” The calculation 55,439/57,048*100% equals to 97.18% and NOT as written 97.25%. The original article has been updated.
CRIS-Team Scopus Importer:2025-05-02

Correction to: The quality of care of the dying in hospital—next-of-kin perspectives (Supportive Care in Cancer, (2020), 10.1007/s00520-020-05465-2) - Heckel, Maria; Vogt, Annika R.; Stiel, Stephanie; Radon, Johannes; Kurkowski, Sandra; Goebel, Swantje; Ostgathe, Christoph; Weber, Martin (Supportive Care in Cancer, 2020)
The surname and name of Christoph (name) Ostgathe (surname) are reversed.
CRIS-Team Scopus Importer:2020-06-05

Costs associated with multidrug-resistance in inpatient palliative care - Adelhardt, Thomas; Hessemer, Stefanie; Heckel, Maria; Herbst, Franziska A.; Stiel, Stephanie; Ostgathe, Christoph; Schöffski, Oliver (Gesundheitsökonomie und Qualitätsmanagement, 2019)
The study deals with the financial impact of the occurrence of multidrug-resistant pathogens on a palliative care unit of a German university hospital. Aims of the study are an analysis of the cost drivers as well as a cost comparison between MDRO-positive and -negative patients.
CRIS-Team WoS Importer:2019-09-17

COVID-19: Challenges and solutions for the provision of care to seriously ill and dying people and their relatives during SARS-CoV-2 pandemic - perspectives of pandemic response team members: A qualitative study on the basis of expert interviews (part of PallPan) - Klinger, Isabell; Heckel, Maria; Shahda, Sophie; Kriesen, Ursula; Schneider, Carolin; Kurkowski, Sandra; Junghanss, Christian; Ostgathe, Christoph (Palliative Medicine, 2022)
Background: During the SARS-CoV-2 pandemic's initial waves, bans on visiting and isolation measures placed limits on providing services for seriously ill and dying people and their relatives. Pandemic response teams at governmental level (macro), at federal state and municipal level (meso) and in healthcare facilities (micro) played their role in pandemic management procedures. Aim: To explore pandemic-related challenges and solutions of pandemic response teams regarding the provision of care to seriously ill and dying people and their relatives. Findings were to be integrated into a national strategy (PallPan). Design: Semi-structured expert interviews (10/2020-2/2021) analysed via structured content analysis. Setting/Participants: We interviewed 41 members, who discussed the work of 43 German pandemic response teams (micro n = 23; meso n = 20; no members were available at macro level) from 14 German federal states. Results: Twenty-nine of 43 teams took account of the needs of seriously ill and dying. Their main challenges resulted from pandemic-related legal requirements in hospitals and long-term care facilities. The implementation of such was in the remits of the meso level. Dysfunctional or non-existent communication between the levels was reported to be challenging. To foster patient-related solutions the micro level pandemic response teams supported individual decisions to enable patient-relative contact for example, visiting and saying goodbye outside, meeting via digital solutions. Conclusions: Pandemic response teams evidently struggled to find appropriate solutions to ease pandemic-related impact on the care of seriously ill and dying patients and their relatives. We recommend bringing palliative care expertise on board.
CRIS-Team WoS Importer:2022-06-24
Keywords: Qualitative research; palliative care; COVID-19; public health; SARS-CoV-2

COVID-19 pandemic response teams: organization, competencies, and challenges-understanding and using structural realities - Klinger, Isabell; Heckel, Maria; Shahda, Sophie; Krisen, Ursula; Stellmacher, Silke; Kurkowski, Sandra; Junghanss, Christian; Ostgathe, Christoph (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2022)
Background and aim. Germany has a federal state system. Pandemic response teams are key instruments of pandemic management. The aim of this article is to describe the structures and powers of pandemic response teams that were explored during a study on the care of the critically ill and dying in times of a pandemic (Pall Pan). The focus is on health-related pandemic response teams on the national state level (macrolevel) and federal and community level (mesolevel) as well as pandemic response teams in healthcare facilities (microlevel).
CRIS-Team WoS Importer:2022-05-13

Dementia patients in palliative care according to data from the German National Hospice and Palliative Care Register (2009–2021) - Donath, Carolin; Ostgathe, Christoph; Heckel, Maria (BMC Palliative Care, 2024)
Background: People with dementia are less in focus of palliative care research than other patient groups even though the awareness of their palliative and end-of-life care needs is rising. Empirical data analyses on people with dementia in palliative care services are lacking. Aim: To explore the prevalence of dementia diagnoses as per the ICD criteria among users of various palliative care settings and to compare use of palliative services, care pathways, and outcomes in people with and without a dementia diagnosis. Design: We conducted retrospective analysis of dementia diagnoses as per ICD (F00-F03/G30) in the German National Hospice and Palliative Care Register between 2009 and 2021. The analysis used methods of descriptive and inferential statistics, including the Bonferroni correction for alpha error inflation. Setting/participants: We limited the analysis to the subsample of people aged over 64. Results: The prevalence of dementia in the different settings of palliative care was lower than in the age-comparable population: Of the 69,116 data sets included in the analysis, a small minority (3.3%) was coded with dementia as the principal diagnosis. Among patients on inpatient palliative care wards, 0.8% (148 of 19,161) had a dementia diagnosis, as did 2.2% (52 of 2,380) of those under hospital palliative care support teams and 4.3% (2,014 of 46,803) of those receiving specialized palliative care at home. Conclusions: The records of the German National Hospice and Palliative Care Register suggest that the prevalence of dementia is lower than one might expect from general population data, though numbers are in line with international studies on proportion of dementia patients receiving palliative care. Future research could usefully examine whether this discrepancy stems either from omissions in coding dementia as patients’ principal diagnosis respectively from lapses in documentation of a dementia diagnosis previously made, or from barriers to accessing palliative care services or even displays being excluded from palliative care when trying to access it. Trial registration: No registration.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Clinical coding; Cognition disorders; Dementia; Documentation; Health services accessibility; Health Services Research; Palliative Care; Palliative Medicine

Development of a Complex Intervention to Support the Use of Sedative Drugs in Specialist Palliative Care (iSedPall) - Kauzner, Saskia; Schneider, Manuela; Heckel, Maria; Klein, Carsten; Bausewein, Claudia; Schildmann, Eva; Bazata, Jeremias; Kolmhuber, Stefanie; Krauss, Sabine H.; Odierna, Beatrice; Rémi, Constanze; Schildmann, Jan; et al. (Palliative Medicine Reports, 2024)
Background: The option of intentional sedation to relieve intolerable suffering from treatment-refractory symptoms may elicit a feeling of safety for patients and informal caregivers as a last resort if the situation becomes unbearable. Many health care professionals feel uncomfortable and insecure in conducting intentional sedation due to specific challenges. We developed a complex intervention to support best practice use of sedative drugs in specialist palliative care in Germany based on previously published recommendations. This article aims at reporting the development of the intervention. Methods: The development of the intervention was based on theory and existing evidence with active stakeholder participation and patient and public involvement, following the updated Medical Research Council (MRC) Framework on complex interventions. A “Theory of Change,” drawing on expert-approved best practice recommendations and applying user-centered methods, fostered the development. The process encompassed study preparation, development of the elements of the intervention, and designing the multimodal intervention. For reporting, we adhere to the Guidance for Reporting Intervention Development framework. Results: The intervention is aimed at health care professionals working in specialist palliative care (inpatient and homecare settings) and consists of several components: (1) a screening tool, (2) the individual elements of the intervention, and (3) educational material for health care professionals to support them using the intervention. Additional information material was developed for patients and informal caregivers. Despite the benefits of stakeholder involvement, we faced some barriers due to limited health care staff and time resources and reservations regarding research in general. Discussion: A pilot study is planned for testing the overall feasibility of the intervention and exploring possible benefits for health care professionals to inform a subsequent fully powered implementation study. To deal with the challenges, we stayed in contact with the health care teams, maintained transparency, and provided opportunities for active participation.
CRIS-Team Scopus Importer:2025-02-04
Keywords: complex intervention; GUIDED; intervention development; palliative care; sedative drugs; theory of change

Development of a national strategy with recommendations for the care of seriously ill and dying people and their relatives in pandemics: A modified Delphi study - Gauder, Sonja; Pralong, Anne; Remi, Constanze; Hodiamont, Farina; Klinger, Isabell; Heckel, Maria; Simon, Steffen T.; Bausewein, Claudia (Palliative Medicine, 2022)
Background: The SARS-CoV-2 pandemic is a constant challenge for health care systems, also in Germany. Care of seriously ill and dying people and their relatives is often neglected and suffering increased due to sub-optimal symptom management, visiting restrictions and lonely dying. The project "Palliative Care in Pandemics (PallPan)" intended to develop a national strategy including evidence- and consensus-based recommendations for the care of seriously ill and dying people and their relatives during pandemic times in Germany. Aim: To reach consensus on evidence-based recommendations for the care of seriously ill and dying people and their relatives in pandemics. Methods: Three-step consensus process comprising two online Delphi rounds and an expert workshop conducted from April to June 2021. One hundred twenty experts from various areas of healthcare, administration, and politics in Germany were included. Results: During the consensus-process, pre-formulated evidence-based recommendations were refined step-by-step. This resulted in consensus on 33 recommendations on the topics of "supporting patients and their relatives," "supporting staff," and "supporting and maintaining structures and provision of palliative care." The recommendations address professional carers and various responsibilities on a governmental, federal state and municipal level, and in healthcare facilities. Conclusion: We provide evidence and consensus-based recommendations for the care of seriously ill and dying people and their relatives in pandemics in Germany. This is an important step towards a pandemic preparedness and hopefully improves the future palliative care response to pandemics.
CRIS-Team WoS Importer:2022-08-26

Development of empirical recommendations for regional hospice and palliative care networks in Germany: A qualitative study - Herbst, Franziska A.; Heckel, Maria; Stiel, Stephanie; Ostgathe, Christoph (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2018)
BACKGROUND: Internationally, efforts are underway to develop coordinated and standardized approaches for palliative care service delivery by improving service quality in hospice and palliative care networks. German legal regulations explicitly demand networking between hospice and palliative care providers. However, there is little research on models of cooperation and the building and development of hospice and palliative care networks. Research-based recommendations for network building and advancement are lacking. OBJECTIVE: The study aim was to develop empirical recommendations for the building of new and advancement of existing hospice and palliative care networks in Bavaria, Germany. METHODS: The project utilized a qualitative approach. The research project was structured in six sequential phases: 1) semi-structured individual interviews on status quo of networks, 2) a workshop including a focus group to develop definitions of key terms and prioritize major network themes, 3) semi-structured face-to-face interviews on factors enabling and inhibiting cooperation, 4) drafting of a recommendation for regional hospice and palliative care networks, 5) an online consensus survey questionnaire to rate relevance and feasibility of the draft recommendation and an internal consensus meeting to revise the draft, and 6) an expert workshop to develop examples of realization. Coordinators and chairpersons of 12 hospice and palliative care networks constitute the study population for study phases 1 to 3, 5, and 6. Network representatives partook in one (n=6), two (n=6), three (n=4), four (n=2), or all five (n=1) of the study phases 1, 2, 3, 5, and 6. Further experts participated in one (n=10) or both (n=1) of the phases 5 and 6. RESULTS: Recommendations were drafted for six thematic fields: (i) missions and aims, (ii) roles and responsibilities, (iii) coordination, (iv) communication and information channels, (v) public visibility, and (vi) funding. The whole set of recommendations was rated by 90% of the participants to be fully or somewhat important for network building and development. A total of 22 recommendations was approved. CONCLUSIONS: The call for establishing and developing standards for hospice and palliative care networks was situated within the current policy climate of Germany and the broader international community. The present recommendations can aid implementation of this request and have a strong relevance for practice.
EVALuna2:35124

Die Beschreibung des Gesundheitszustandes anhand von Veränderungen in Bewegungsmustern von Palliativpatient:innen – Eine explorative Erfassung - Yip, Julia; Steigleder, Tobias; Heckel, Maria; Eskofier, Björn; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2022)

Die Entstehung einer professionalisierten Fachkultur in der Palliativmedizin - sprachwissenschaftliche Perspektiven - Peters, Joachim; Heckel, Maria; Ostgathe, Christoph; Habermann, Mechthild (12. Kongress der Deutschen Gesellschaft für Palliativmedizin, 2018)

Documentation of Sedation in Palliative Care: A Scoping Review of Requirements, Recommendations, and Templates - Kauzner, Saskia; Heckel, Maria; Ostgathe, Christoph; Schneider, Manuela; Bausewein, Claudia; Schildmann, Eva; Kremling, Alexander; Ziegler, Kerstin; Klein, Carsten (Journal of Palliative Medicine, 2023)
Objective: To identify and describe requirements, recommendations, and templates for the documentation of sedation in adult palliative care.Introduction: International literature shows inconsistency in clinical practice regarding sedation in palliative care accompanied by legal, ethical, and medical uncertainties. Documentation in general serves as proof for previous treatments. In the context of intentional sedation to relieve suffering at the end of life, documentation provides a clear demarcation against practices of euthanasia.Inclusion Criteria: Articles with full-text version published in English or German since 2000, covering documentation requirements, recommendations, monitoring parameters or templates for sedation in adult palliative care were included.Methods: Scoping review following the JBI methodology. Search in online databases, websites of professional associations in palliative care, reference lists of relevant publications, the archive of the German "Journal of Palliative Medicine" and databases for unpublished literature were used. Search terms included "palliative care,' "sedation," and "documentation." The search was conducted from January 2022 to April 2022 with an initial hand search in November 2021. Data were screened and charted by one reviewer after conducting a pilot test of the criteria.Results: From the initial 390 articles (database search), 22 articles were included. In addition, 15 articles were integrated from the hand search. The results can be clustered in two sets of items, regarding either the documentation before or during sedation. The documentation requirements referred both to inpatient and homecare settings but in many cases, a clear assignment was missing.Conclusions: The guidelines analyzed in this study rarely cover setting-specific differences in documentation and often treat documentation as minor topic. Further research is needed addressing legal and ethical concerns of health care teams and, therefore, help to improve treatment of patients suffering from otherwise intractable burden at the end of life.
CRIS-Team WoS Importer:2023-05-26

Effects of Methicillin-Resistant Staphylococcus aureus/Multiresistant Gram-Negative Bacteria Colonization or Infection and Isolation Measures in End of Life on Family Caregivers: Results of a Qualitative Study - Heckel, Maria; Sturm, Alexander; Herbst, Franziska A.; Ostgathe, Christoph; Stiel, Stephanie (Journal of Palliative Medicine, 2017)
Little is known about the experiences of family caregivers of hospitalized patients with confirmed methicillin-resistant Staphylococcus aureus/multiresistant gram-negative bacteria (MRSA/MRGN) diagnosis at the end of life. The study at hand is a subproject of an interdisciplinary cooperation project that aims at developing a patient-, family-, and team-centered approach in dealing with MRSA/MRGN-positive hospitalized patients in palliative and geriatric care.The present study aimed to assess the individual effects of the patient's MRSA/MRGN colonization or infection and isolation measures on family caregivers.Between April 2014 and September 2015, all known family caregivers associated with an MRSA/MRGN-positive patient from a palliative care unit, a hospital palliative care support team, and a geriatric ward were considered for study participation. A qualitative interview study with family caregivers and an additional focus group was conducted. Data were analyzed using the principles of Grounded Theory.Family caregivers (N = 62) raised suggestions regarding the provision of information and communication on the MRSA/MRGN diagnosis and hygiene measures from staff members and the consistency of hygiene procedures. Family caregivers requested not to be stigmatized or being disadvantaged due to the MRSA/MRGN diagnosis of the patient, and they wished to receive psychosocial and emotional support.Staff members and institutional stakeholders should be aware that family caregivers might be burdened and upset by positive MRSA/MRGN diagnosis and the required hygiene measures. The need for detailed and understandable information on MRSA/MRGN, adequate communication between staff members and family caregivers, and support for family caregivers should be of special attention in particular in end-of-life care.
EVALuna2:26215

End-of-life care research with bereaved informal caregivers - Analysis of recruitment strategy and participation rate from a multi-centre validation study - Stiel, Stephanie; Heckel, Maria; Bussmann, Sonja; Weber, Martin; Ostgathe, Christoph (BMC Palliative Care, 2015)
Background: One essential element of research is the successful recruitment of participants. However, concerns are obvious regarding the ethical implications of involving terminally ill and even dying patients and their informal caregivers as research participants. This study aims to illustrate central issues encountered when recruiting bereaved informal caregivers for a questionnaire validation study on the quality of dying and death. Methods: Between July 2012 and November 2013, informal caregivers of deceased inpatients who were treated at two palliative care units in Germany were invited to participate in a questionnaire validation study. Informal caregivers were called by a trained researcher at the end of the fourth week after death at the earliest and by the sixteenth week after death at the latest and asked to participate in a face-to-face interview in their private home. Results: The overall participation rate of all eligible informal caregivers was 76.1% (226/297). The mean burden score was 2.5 (NRS from 0 = no burden to 10 = maximum burden; n = 221). Higher burden scores (≥4) were associated with emotional and burdensome memories (n = 34) being invoked throughout the interview. Severe or maximum burden scores (≥7) were stated by 13.2% of participants. The average time between the associated patient's death and the informal caregiver's interview was 57.3 days (range 26-176 days, median 49.5 days). 5.3% of all 226 interviews were not completed due to different reasons. Participants' comments on the way in which the study was conducted gave insight into their motivation to take part in the study and their evaluation of the interview situation. Conclusions: The recruitment strategy can be recommended to other researchers developing research with bereaved carers. The burden caused by study participation was acceptable to the researchers carrying out this research, although a small group of participants experienced high levels of burden which should be anticipated and appropriate support services offered. Family caregivers are willing to support end-of-life care research, have different motivations for participation and even reported benefits from participation. Nevertheless, study designs have to take into account and ease the potential burden of interviews for caregivers experiencing grief.
Keywords: Assessment tool; Distress; Informal caregiver; Motivation; Palliative care; Participation rate; Quality of dying and death; Recruitment; Research participation; Validation; Willingness

Entwicklung einer Applikation zum Home-Monitoring des Gesundheitszustandes von Palliativpatienten - eine Proof-of-Concept-Studie - Sternemann, Ulla; Suchantke, Insa; Schmidt, Klaus-Günther; Höfner, Patrick; Wagner, Daniel; Ollenschläger, Malte; Heckel, Maria; Ostgathe, Christoph; Eskofier, Björn; Steigleder, Tobias (Zeitschrift für Palliativmedizin 2020; 21(05), 2020)
Fragestellung: Der Bedarf an spezialisierter ambulanter Palliativversorgung (SAPV) steigt bei abnehmenden Ressourcen. Um eine flächendeckende Versorgung zu gewährleisten, können digitale Systeme Patienten und Fachpersonal unterstützen. Wir erforschen eine Smartphone Applikation (App) und Web-Interface (WI) die gewährleisten sollen, dass Patienten und SAPV Zugriff auf biometrische und psychometrische Daten haben, um die Versorgung möglichst Ressourcen-effizient zu gestalten. Studiendesign: Explorative Anwendungs- und Proof-of-Concept-Studie mit Probanden Methodik: App und WI Entwurf nach klinisch-medizinischen Vorgaben von erfahrenen Palliativmedizinern integriert psychometrische (MIDOS_2) und exemplarische biometrische Messung (Körpergewicht (KG), Körperflüssigkeitsanteil (KFA), Blutdruck (BD)) mit automatischer (Bluetooth) und manueller Eingabe; Evaluation des ersten Design-Modells der App in begleitender Beobachtung; offenes Interview mit n = 2 Probanden (männlich, Alter 70-85);Implementierung des Feedbacks; Pilotierung mit n = 6 Probanden (2 weiblich, Alter 23-30); Ergebnis: Erster Entwurf nach klinisch-medizinischen Vorgaben: App: KG des Patienten wird automatisch und KF, BD, MIDOS_2 manuell eingegeben. Die Daten werden in App und WI visuell individuell anpassbar dargestellt. App wurde nach begleitender Beobachtung hinsichtlich Akzeptanz und Nutzbarkeit überarbeitet: vereinfachte Nutzerschnittstelle. Pilotierung mit Probanden: Dateneingabe, -übertragung, -abruf und webbasierter Zugriff erfolgten in 100 % der Fälle fehlerfrei. Anwendungsdauer für KG, KFA, BD, MIDOS_2 betrug im Durchschnitt 4 min. Diskussion: Austausch von psychometrischen und biometrischen Daten zwischen Patient (App) und SAPV-Team (WI) werden ermöglicht und so können SAPV Teams bei ihrer Behandlungsplanung unterstützet werden. Take Home Message für die Kongressbesucher: App und WI kann die SAPV effizienter gestalten. Weitere Untersuchungen mit Patienten sind notwendi
Keywords: Palliativmedizin; SAPV; Smartphone

Erratum to: Mitbetreuung der Angehörigen von Patient:innen mit einer nicht heilbaren Krebserkrankung im Erkrankungsverlauf (Die Onkologie, (2024), 30, 11, (1053-1061), 10.1007/s00761-024-01587-y) - Oechsle, Karin; Berendt, Julia; Gebert, Tanja; Heckel, Maria; Hentschel, Leopold; Hornemann, Beate; Jentschke, Elisabeth; Neukirchen, Martin; van Oorschot, Birgitt; Rechenmacher, Michael; Schnabel, Astrid; Simon, Steffen; et al. (Die Onkologie, 2025)
Im elektronischen Zusatzmaterial wurden ursprünglich falsche Dateien mit dem Artikel veröffentlicht. Sie wurden durch die richtigen Dateien ersetzt. Der Originalbeitrag wurde korrigiert.
CRIS-Team Scopus Importer:2025-04-25

Erratum to: SOP – Mitbetreuung der Angehörigen von Patient:innen mit einer nicht heilbaren Krebserkrankung in der Sterbephase (Die Onkologie, (2024), 30, 10, (976-984), 10.1007/s00761-024-01585-0) - Oechsle, Karin; Berendt, Julia; Gebert, Tanja; Heckel, Maria; Hentschel, Leopold; Hornemann, Beate; Jentschke, Elisabeth; Neukirchen, Martin; van Oorschot, Birgitt; Rechenmacher, Michael; Schnabel, Astrid; Simon, Steffen; et al. (Die Onkologie, 2025)
Im elektronischen Zusatzmaterial wurden ursprünglich falsche Dateien mit dem Artikel veröffentlicht. Sie wurden durch die richtigen Dateien ersetzt. Der Originalbeitrag wurde korrigiert.
CRIS-Team Scopus Importer:2025-04-25

Evaluating the implementation of national recommendations on multidrug-resistant bacterial microorganisms in end-of-life care - Heckel, Maria; Illig, Annabell; Brunner, Sarah; Ostgathe, Christoph (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2020)
Introduction: In 2017, a national recommendation on multidrug-resistant bacterial microorganisms (MDRO) in end-of-life care was published. In order to monitor the implementation in a hospital-based palliative care unit, a dedicated multidisciplinary working group on MDRO was established. It developed a standard operating procedure and a documentation template (checklist). The aim of the present study is to evaluate the implementation status after one year. Methods: A mixed-methods approach was selected. The status of implementation was identified through a survey among staff members. A retrospective routine data analysis was performed. A focus group discussion with members of the working group focused on previous steps, factors conducive to implementation and on remaining problems. Results: Almost all (18 out of 20) participants (20 out of 29 eligible staff members) knew the national recommendations. Twelve out of 27 recommendations had a high degree of implementation after one year, another 13 recommendations were seen as at least partly integrated into daily routine. For two recommendations the degree of implementation was rated low: (i) ”Taking into account any additional time constraint imposed by protection and isolation measures when planning for personnel and bed occupancy”, and (ii) ”Facilitating the patient's ability to distinguish and recognize team members and family caregivers”. Working group members reported improvements since the implementation, whilst reporting some uncertainty prevailing among both staff members and visitors. Inhibitory factors were said to include the complexity of the standard operating procedure, inadequate usage and poor usability of the checklist. Behavioural and cognitive barriers such as anxieties related to transmission and the sense of security caused by the routine use of protective clothing were considered to be strong. Improving the checklist and the standard operating procedure as well as anchoring procedures in daily routine were considered to be the next important steps. Discussion: The implementation of recommendations is an iterative process and requires the ongoing development of appropriate measures for implementation in the respective institution. A multidisciplinary working group with monitoring tasks is an advantage.
CRIS-Team Scopus Importer:2020-11-20
Keywords: End-of-life care; Evaluation research; Infection control; Palliative care; Patient safety

Expert-approved best practice recommendations on the use of sedative drugs and intentional sedation in specialist palliative care (SedPall) - Ostgathe, Christoph; Bausewein, Claudia; Schildmann, Eva; Bazata, Jeremias; Handtke, Violet; Heckel, Maria; Klein, Carsten; Kremling, Alexander; Kurkowski, Sandra; Meesters, Sophie; Seifert, Andreas; Torres Cavazos, Jorge; et al. (BMC Palliative Care, 2023)
Background: The use of sedative drugs and intentional sedation in end-of-life care is associated with clinical, ethical and legal challenges. In view of these and of the issue’s great importance to patients undergoing intolerable suffering, we conducted a project titled SedPall (“From anxiolysis to deep continuous sedation – Development of recommendations for sedation in palliative care“) with the purpose of developing best practice recommendations on the use of sedative drugs and intentional sedation in specialist palliative care and obtaining feedback and approval from experts in this area. Design: Our stepwise approach entailed drafting the recommendations, obtaining expert feedback, conducting a single-round Delphi study, and convening a consensus conference. As an interdisciplinary group, we created a set of best practice recommendations based on previously published guidance and empirical and normative analysis, and drawing on feedback from experts, including patient representatives and of public involvement participants. We set the required agreement rate for approval at the single-round Delphi and the consensus conference at ≥80%. Results: Ten experts commented on the recommendations’ first draft. The Delphi panel comprised 50 experts and patient and public involvement participants, while 46 participants attended the consensus conference. In total, the participants in these stages of the process approved 66 recommendations, covering the topics “indications”, “intent/purpose [of sedation]”, “decision-making”, “information and consent”, “medication and type of sedation”, “monitoring”, “management of fluids and nutrition”, “continuing other measures”, “support for relatives”, and “team support”. The recommendations include suggestions on terminology and comments on legal issues. Conclusion: Further research will be required for evaluating the feasibility of the recommendations’ implementation and their effectiveness. The recommendations and the suggested terminology may serve as a resource for healthcare professionals in Germany on the use of sedative drugs and intentional sedation in specialist palliative care and may contribute to discussion on the topic at an international level. Trial Registration: DRKS00015047 (German Clinical Trials Register)
CRIS-Team Scopus Importer:2023-09-15
Keywords: Community-based participatory research; Empirical research; Hypnotics and sedatives; Palliative care; Practice guidelines; Terminal care

German measurements for family caregiver need assessment A narrative review on available self-assessments measuring different dimensions of family caregiver needs - Oubaid, Nikolas; Ullrich, Anneke; Schwenzitzki, Lisa; Berendt, Julia; Heckel, Maria; Hentschel, Leopold; Hornemann, Beate; Jentschke, Elisabeth; Pauli, Berenike; Simon, Steffen T.; Stiel, Stephanie; Van Oorschot, Birgitt; et al. (Onkologe, 2022)
Background Today, guideline-based care for patients with advanced cancer includes regular assessment of needs, not only for patients, but also for their family caregivers. Objectives Identification, evaluation and short description of German validated self-assessment instruments for needs assessment of family caregivers that can be used in daily practice. Materials and methods This narrative review is based on a syntax-based systematic literature search in PubMed (November 2021). Results The literature search identified 525 articles dealing with needs assessment for family caregivers. A multistep, criterion-referenced process identified 12 self-assessment instruments. These 12 capture (partly) the needs of family caregivers in terms of overall burden, psychosocial burden and psychopathological symptoms, quality of life, and support needs. They are available in German, validated, practicable in daily use, and easily accessible. The instruments-including their short versions-are presented with relevant information on use, target parameters, author references, availability, and evaluation. Conclusion This article can be helpful for practitioners wishing to implement a guideline-compliant, regular needs assessment of caregivers and to promote the provision of concrete support services. However, these instruments only cover individual aspects of possible needs of caregivers and it remains to be assessed how the 12 instruments can be combined for routine use or how a selection can be made.
CRIS-Team WoS Importer:2022-04-22

Health- and disease-related data of inpatients in palliative care units of the Comprehensive Cancer Centers and other hospitals in comparison-Data from the Hospice and Palliative Care Register - Brunner, Sarah; Heckel, Maria; Zenz, Daniel; Ostgathe, Christoph; Gahr, Susanne (Wiener Medizinische Wochenschrift, 2022)
Background The National Hospice and Palliative Registry is a database for palliative care facilities documenting a core data set for quality assurance and scientific evaluations. Objectives The study aims identifying differences between patients in palliative care units treated in Comprehensive Cancer Centers (CCC) or other hospitals (OH) focussing on sociodemographic and health/disease-related characteristics. Methods Descriptive data analysis using IBM SPSS Statistics 21 included patients treated from 2014 to 2018. Comparisons included sociodemographic data, diagnoses, ECOG status and treatment duration. Results 12,922 patient data were analyzed (CCC n = 4975/OH = 7947). In CCCs 79.8% had a tumor diagnosis, in other hospitals 85.1%. The proportion of patients with ECOG 4 was higher in CCCs than in other hospitals. The average length of stay in CCCs was 12.6 days, in other hospitals 11.3 days (p = 0.023). Conclusions Data show differences between patients in palliative care implicating CCCs treating more complex palliative care patients than other hospitals.
CRIS-Team WoS Importer:2022-02-11

Hospital end-of-life care: Families' free-text notes - Kurkowski, Sandra; Radon, Johannes; Vogt, Annika R.; Weber, Martin; Stiel, Stephanie; Ostgathe, Christoph; Heckel, Maria (BMJ Supportive & Palliative Care, 2020)
Background: Palliative care strives to improve quality of life for patients with incurable diseases. This approach includes adequate support of the patients' loved ones. Consequently, loved ones have personal experiences of providing end-of-life care for their next. This is a resource for information and may help to investigate the loved ones' perspectives on need for improvements. Aim: To identify further quality aspects considered important by loved ones to improve the quality of care at the end of life as an addition to quantitative results from the Care of the Dying Evaluation for the German-speaking area (CODE-GER) questionnaire. Design: Within the validation study of the questionnaire â € Care of the Dying Evaluation' (CODETM) GER, loved ones were asked to comment (free text) in parallel on each item of the CODE-GER. These free-text notes were analysed with the qualitative content analysis method by Philipp Mayring. Setting/participants: Loved ones of patients (n=237), who had died an expected death in two university hospitals (palliative and non-palliative care units) during the period from April 2016 to March 2017. Results: 993 relevant paragraphs were extracted out of 1261 free-text notes. For loved ones, important aspects of quality of care are information/communication, respect of the patient's and/or loved one's will, involvement in decision-making at the end of life (patient's volition) and having the possibility to say goodbye. Conclusions: It is important for loved ones to be taken seriously in their sorrows, to be informed, that the caregivers respect the patients' will and to be emotionally supported. Trial registration number: This study was registered at the German Clinical Trials Register (DRKS00013916).
CRIS-Team Scopus Importer:2020-12-11
Keywords: hospital care; quality of life; service evaluation; social care; supportive care; terminal care

Identifying the need for specialized palliative care in adult cancer patients - Development and validation of a screening procedure based on proxy assessment by physicians and filter questions - Ostgathe, Christoph; Wendt, Kim N.; Heckel, Maria; Kurkowski, Sandra; Klein, Carsten; Krause, Stefan; Fuchs, Florian; Bayer, Christian M.; Stiel, Stephanie (BMC Cancer, 2019)
Background: One challenge in caring for cancer patients with incurable disease is the adequate identification of those in need for specialized palliative care (SPC). The study's aim was to validate an easy to use phenomenological screening tool. Methods: The German tool is based on the National Comprehensive Cancer Network (NCCN) Palliative Care guidelines and contains ten items in five domains that focus e.g. on diagnosis, functional status, complications, comorbidities, and palliative care relevant problems such as symptom management, distress, and support of family and team members. Sum score ranges from 0 to 14 (no need to great need). Assessment to identify SPC needs was done in university hospital wards between 1 and 08/2017 by health care professionals on admission of the patient if the disease was incurable and expected prognosis < 12 months. The Integrated Palliative Outcome Scale (IPOS, staff version), an outcome assessment instrument for palliative care that consists of ten items, served as external criterion; in sub samples inter-rater/test-retest were performed. Results: Data from 208 patients with incurable disease and life expectancy < 12 months (54.8% female; average age 63.5 years, range 21-96) were assessed using the tool. The tool has good convergent validity; the correlation between the sum scores of IPOS and our tool showed a significant and substantial effect. The sum score was independent of the patient's age, gender and primary diagnosis. Patients who already were in contact with SPC had significantly higher screening scores than patients without. With a cut point of ≥ 5, 80.8% of the screened patients were in need for SPC. Cronbach's alpha was α =.600. Rater agreement (inter-rater, test-retest) varied between single items. Correlation coefficients showed significant substantial effects. Conclusions: This is the first validation of a screening procedure in German language identifying SPC needs of adult patients with advanced cancer and the first using filter questions as a pre-screening. Proxy assessment of SPC needs by physicians in cancer care settings is feasible and the suggested tool presents a valid instrument to trigger a PC consultation. Trial registration: The study was not registered.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Cancer; Delivery of health care; Needs assessment; Palliative care; Psychometric properties

Improving Dyspnoea Symptom Control of Patients in Palliative Care Using a Smart Patch-A Proof of Concept Study - Kamal Mallick, Mostafa; Biser, Sarah; Haridas, Aathira; Umesh, Vaishnavi; Toensing, Olaf; Abdullahi, Imrana; Ollenschläger, Malte; Heckel, Maria; Kluge, Felix; Ostgathe, Christoph; Eskofier, Björn; Steigleder, Tobias (Frontiers in Digital Health, 2021)
The world of healthcare constantly aims to improve the lives of people while nurturing their health and comfort. Digital health and wearable technologies are aimed at making this possible. However, there are numerous factors that need to be addressed such as aging, disabilities, and health hazards. These factors are intensified in palliative care (PC) patients and limited hospital capacities make it challenging for health care providers (HCP) to handle the crisis. One of the most common symptoms reported by PC patients with severe conditions is dyspnoea. Monitoring devices with sufficient comfort could improve symptom control of patients with dyspnoea in PC. In this article, we discuss the proof-of-concept study to investigate a smart patch (SP), which monitors the pulmonary parameters: (a) breathing rate (BR) and inspiration to expiration ratio (I:E); markers for distress: (b) heart rate (HR) and heart rate variability (HRV), and (c) transmits real-time data securely to an adaptable user interface, primarily geared for palliative HCP but scalable to specific needs. The concept is verified by measuring and analyzing physiological signals from different electrode positions on the chest and comparing the results achieved with the gold standard Task Force Monitor (TFM).
Keywords: wearable devices; dyspnoea; smart patch; palliative care; digital health

Intercountry and intracountry variations in opinions of palliative care specialist physicians in Germany, Italy, Japan and UK about continuous use of sedatives: an international cross-sectional survey - Morita, Tatsuya; Kawahara, Takuya; Stone, Patrick; Sykes, Nigel; Miccinesi, Guido; Klein, Carsten; Stiel, Stephanie; Hui, David; Deliens, Luc; Heijltjes, Madelon T.; Mori, Masanori; Heckel, Maria; et al. (BMJ Open, 2022)
OBJECTIVES: To explore intercountry and intracountry differences in physician opinions about continuous use of sedatives (CUS), and factors associated with their approval of CUS. SETTINGS: Secondary analysis of a questionnaire study. PARTICIPANTS: Palliative care physicians in Germany (N=273), Italy (N=198), Japan (N=334) and the UK (N=111). PRIMARY AND SECONDARY OUTCOME MEASURES: Physician approval for CUS in four situations, intention and treatment goal, how to use sedatives and beliefs about CUS. RESULTS: There were no significant intercountry or intracountry differences in the degree of agreement with statements that (1) CUS is not necessary as suffering can always be relieved with other measures (mostly disagree); (2) intention of CUS is to alleviate suffering and (3) shortening the dying process is not intended. However, there were significant intercountry differences in agreement with statements that (1) CUS is acceptable for patients with longer survival or psychoexistential suffering; (2) decrease in consciousness is intended and (3) choice of neuroleptics or opioids. Acceptability of CUS for patients with longer survival or psychoexistential suffering and whether decrease in consciousness is intended also showed wide intracountry differences. Also, the proportion of physicians who agreed versus disagreed with the statement that CUS may not alleviate suffering adequately even in unresponsive patients, was approximately equal. Regression analyses revealed that both physician-related and country-related factors were independently associated with physicians' approval of CUS. CONCLUSION: Variations in use of sedatives is due to both physician- and country-related factors, but palliative care physicians consistently agree on the value of sedatives to aid symptom control. Future research should focus on (1) whether sedatives should be used in patients with longer survival or with primarily psychoexistential suffering, (2) understanding physicians' intentions and treatment goals, (3) efficacy of different drugs and (4) understanding the actual experiences of patients receiving CUS.
CRIS-Team Scopus Importer:2022-05-06
Keywords: adult palliative care; medical ethics; palliative care

Interrater agreement of multi-professional case review as reference standard for specialist palliative care need: a mixed-methods study - Müller, Evelyn; Müller, Michael Josef; Seibel, Katharina; Boehlke, Christopher; Schäfer, Henning; Klein, Carsten; Heckel, Maria; Simon, Steffen T.; Becker, Gerhild (BMC Palliative Care, 2023)
Background: A wide variety of screening tools for the need for specialist palliative care (SPC) have been proposed for the use in oncology. However, as there is no established reference standard for SPC need to compare their results with, their sensitivity and specificity have not yet been determined. The aim of the study was to explore whether SPC need assessment by means of multi-professional case review has sufficient interrater agreement to be employed as a reference standard. Methods: Comprehensive case descriptions were prepared for 20 inpatients with advanced oncologic disease at the University Hospital Freiburg (Germany). All cases were presented to the palliative care teams of three different hospitals in independent, multi-professional case review sessions. The teams assessed whether patients had support needs in nine categories and subsequently concluded SPC need (yes / no). Interrater agreement regarding SPC need was determined by calculating Fleiss’ Kappa. Results: In 17 out of 20 cases the three teams agreed regarding their appraisal of SPC need (substantial interrater agreement: Fleiss’ Kappa κ = 0.80 (95% CI: 0.55–1.0; p < 0.001)). The number of support needs was significantly lower for patients who all teams agreed had no SPC need than for those with agreed SPC need. Conclusions: The proposed expert case review process shows sufficient reliability to be used as a reference standard. Key elements of the case review process (e.g. clear definition of SPC need, standardized review of the patients’ support needs) and possible modifications to simplify the process are discussed. Trial registration: German Clinical Trials Register, DRKS00021686, registered 17.12.2020.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Neoplasms; Palliative care; Psychometrics; Referral and consultation

Knowledge and Public Perception of Palliative Care in Germany - Heckel, Maria; Peters, Joachim; Schweighart, Susanna; Habermann, Mechthild; Ostgathe, Christoph (Journal of palliative medicine, 2024)
Background: Literature reviews reveal poor knowledge and awareness of palliative care in the public. Health literacy deficits impact access to palliative care. Objectives: The aim of this manuscript is to explore the public perception of palliative care in Germany. Design: Triangulated qualitative research design: a snowball-spread online survey and a random pedestrian survey. Setting/Subjects: Citizens in Germany. Results: The pedestrian survey (n = 100) revealed 34% of the participants being not familiar with palliative care. The online survey (n = 994) 5.7% of participants reported to not know what palliative care was. The public's perception of palliative care is mainly medicine oriented, referring to inpatient care for the immediately dying; however, further significant misperceptions were scarce. Conclusions: The public perception shows an indistinct picture of palliative care, and some misconceptions about the objectives and areas of responsibility of the subject, meanwhile, palliative care is known to a majority of people. Understanding partly incomplete pictures of patients and relatives may help to react appropriately in staff-patient interactions and improve public relations.
CRIS-Team Scopus Importer:2024-04-26
Keywords: attitudes; health knowledge; health literacy; palliative care; practice; public health; terminal care

Kompetenzdarstellung, Patientennähe und Argumentationsstrategien von Internetangeboten deutscher Hospize, Palliativstationen und SAPV-Teams-eine korpusbasierte Meta-Analyse - Peters, Joachim; Dykes, Nathan; Ostgathe, Christoph; Habermann, Mechthild; Heckel, Maria (Zeitschrift für Palliativmedizin, 2020)

Kontinuierliche berührungslose Erfassung von Herzschlag und Atmung als Surrogatparameter für Symptomlinderung–eine Pilotstudie - Steigleder, Tobias; Malessa, Anke; Shi, Kilin; Michler, Fabian; Schellenberger, Sven; Heckel, Maria; Kölpin, Alexander; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2018)
Fokus der Palliativmedizin (PM) ist die persönliche Begegnung. Häufig wird bei schwerer Krankheit auf apparative Therapie und Diagnostik verzichtet. Dennoch könnten Biomarker (BM, zB Herz-und Atemfrequenz) wichtige ergänzende Hinweise auf Symptomlast und zur individuellen Anpassung der medikamentösen Behandlung geben. Wir erforschen den innovativen Ansatz, BM mit Radartechnologie (RT) berührungs-und belastungsfrei zu erfassen. Ziel soll es ua in sein, in Zukunft die Symptomlinderung zu verbessern. RT, die auf einem interferometrischem Verfahren beruht, erfasst Herzschläge und Atmung mittels Messung der Distanzänderung zu der Radarantenne aus einigen Metern Entfernung und durch Materialen wie Kleidung oder Bettdecke hindurch. Lernende Algorithmen extrahieren die spezifischen Signale und werten sie automatisiert au

Kosten von multiresistenten Erregern in der stationären Palliativversorgung - Adelhardt, Thomas; Hessemer, Stefanie; Heckel, Maria; Herbst, Franziska A.; Stiel, Stephanie; Ostgathe, Christoph; Schöffski, Oliver (Gesundheitsökonomie und Qualitätsmanagement, 2018)
Multiresistente Erreger (MRE) stellen deutsche Krankenhäuser neben medizinischen Herausforderungen wie einer erhöhten Mortalität und Morbidität der betroffenen Patienten auch vor finanzielle Herausforderungen. Vor dem Hintergrund einer Zunahme des Wettbewerbs und damit auch einem steigenden Kostendruck müssen Krankenhäuser wirtschaftlich handeln. Hierzu ist zentral, die Kostenstruktur detailliert zu erfassen. Einige Studien beschäftigten sich bereits mit Kosten, die durch MRE verursacht wurden. Gerade bei der Behandlung von Menschen am Ende des Lebens ergibt sich hieraus ein Spannungsverhältnis zwischen Effizienz auf der einen und bestmöglicher Pflege bzw. Begleitung von Patienten auf der anderen Seite. Untersuchungen zeigten auch, dass auf Palliativstationen die Prävalenz von multiresistenten Erregern wie zum Beispiel MRSA-Kolonisationen gegenüber dem Krankenhausdurchschnitt deutlich erhöht ist. Eine systematische Literaturrecherche zu diesem Thema ergab, dass mit Ausnahme einer Studie keine Publikationen zur Analyse der durch multiresistente Erreger zusätzlich verursachten Kosten im palliativen bzw. geriatrischen Kontext existieren. Die benannte Veröffentlichung betrachtet dabei die Kostensituation bei der Behandlung von Patienten am Lebensende auf einer geriatrischen Station. Anhand der hier vorliegenden Studie werden die zusätzlich durch MRE entstehenden Kosten bei der Behandlung von Patienten am Ende des Lebens auf einer Palliativstation analysiert und mögliche Kostentreiber identifiziert. Die vorliegende Analyse wurde im Rahmen des multizentrischen Projekts „Untersuchung der Auswirkungen von Infektionen oder Kolonisationen mit MRSA oder anderen multiresistenten Erregern auf Patienten am Lebensende“ durchgeführt. Hintergrund des Gesamtprojektes, „MRSA in End-of-Life Care“ (M-EndoL, BMBF-Projektnummer 01GY1314), ist die Entwicklung eines wissenschaftlich fundierten, patienten- und familienzentrierten Ansatzes zum Umgang mit hospitalisierten Patienten mit MRE-Nachweis am Lebensend

Language in Motion - Time-Typical Vocabulary of Palliative Medicine - Peters, Joachim; Heckel, Maria; Habermann, Mechthild; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2019)
Background Modern palliative medicine is a young discipline that has developed its independent profile with specific guiding concepts, goals and values. The history of the subject and the development of a palliative vocabulary can be explored by analysing specialised publications.
CRIS-Team WoS Importer:2019-05-28

M-EndoL: MRSA in der Versorgung am Lebensende - Untersuchung der Auswirkungen von MRSA- (oder andere multiresistente Keim-) Kolonisation oder Infektion auf Patienten am Lebensende, deren Angehörige, Teammitglieder und Einrichtungen - Ostgathe, Christoph; Lang, Frieder; Bogdan, Christian; Sieber, Cornel; Schöffski, Oliver; Stiel, Stephanie; Heckel, Maria; Tiedtke, Johanna; Sturm, Alexander; Adelhardt, Thomas (Zeitschrift für Palliativmedizin, 2014)

Metaphors for multidrug-resistant bacteria in German newspaper articles, 1995-2015. A computer-assisted qualitative study. - Peters, Joachim; Dykes, Nathan; Habermann, Mechthild; Ostgathe, Christoph; Heckel, Maria (Metaphor and the Social World, 2019)

Mitbetreuung der Angehörigen von Patient:innen mit einer nicht heilbaren Krebserkrankung im Erkrankungsverlauf - Oechsle, Karin; Berendt, Julia; Gebert, Tanja; Heckel, Maria; Hentschel, Leopold; Hornemann, Beate; Jentschke, Elisabeth; Neukirchen, Martin; van Oorschot, Birgitt; Rechenmacher, Michael; Schnabel, Astrid; Simon, Steffen; et al. (Die Onkologie, 2024)
CRIS-Team Scopus Importer:2025-02-04

Mit Bürgerinnen und Bürgern über Forschung und technische Innovationen in der Palliativversorgung ins Gespräch kommen – Pilotierung eines ELSI-Cafés - Öhl, Natalie; Weisser, Alina; Ott, Tabea; Grießhammer, Stefan; Yip, Julia; Klinger, Isabell; Kölpin, Alexander; Miehling, Jörg; Bräuning, J.; Dabrock, Peter; Steigleder, Tobias; Ostgathe, Christoph; et al. (Zeitschrift für Palliativmedizin, 2024)

Mixed-methodical Study Designs in Palliative Research - Heckel, Maria; Kremeike, Kerstin; Stiel, Stephanie; Herbst, Franziska A. (Zeitschrift für Palliativmedizin, 2020)
Entscheidend fur die Methodenwahl ist die Passung zur Forschungsfrage. Gemischt-methodische Ansatze sind als drittes Forschungsparadigma neben qualitativen und quantitativen Herangehensweisen einzuordnen. Sie haben zum Ziel, ein inhaltlich breites und tiefes Verstandnis uber den Forschungsgegenstand zu gewinnen und durch die Kombination der Starken gleichzeitig die Schwachen der Methoden auszugleichen.
CRIS-Team WoS Importer:2020-07-17

More Barriers than Bridges - Research in Times of the GDPR - Kurkowski, Sandra; Ziegler, Kerstin; Jäger, Christian; Torres Cavazos, Jorge; Heckel, Maria; Klein, Carsten; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2022)
CRIS-Team WoS Importer:2022-03-18

MRE-Kolonisation oder -Infektion in der Versorgung von Menschen am Lebensende (End-of-Life Care): Handlungsanweisungen und Informationsmaterialien in zwei deutschen Krankenhäusern - Eine Dokumentenanalyse - Adelhardt, Thomas; Heckel, Maria; Stiel, Stephanie; Ostgathe, Christoph; Schöffski, Oliver (Zeitschrift für Palliativmedizin, 2016)
Hintergrund: Die Auswirkungen von Kolonisation oder Infektion mit multiresistenten Erregern (MRE) und der Isolationsmaßnahmen auf Patienten am Lebensende, deren Angehörige sowie andere Beteiligte innerhalb des Gesundheitswesens sind unbekannt. Ziel der Studie: Die vorliegende Studie beschäftigt sich mit der Frage, inwieweit die speziellen Anforderungen von Patienten am Ende des Lebens in den aktuellen Leitlinien der beteiligten Krankenhäuser Berücksichtigung finden. Langfristig sollen dabei gewonnene Erkenntnisse über Struktur und Aufbau der analysierten Dokumente dazu beitragen, innerhalb des Gesamtprojekts allgemeingültige Verfahrensanweisungen für die oben angeführte Problematik zu definieren und zu etablieren. Methodik: Eine Dokumentenanalyse der Leitfäden und Informationsunterlagen von 2 deutschen Krankenhäusern zum Umgang mit MRE-positiven Patienten wurde durchgeführt. Nach Zuordnung zu Dokumentensets erfolgte eine Analyse mittels inhaltsanalytischem Vorgehen. Die daraus entstandene Codestruktur wurde deskriptiv und inhaltlich bezüglich der Zielgruppen der Dokumente analysiert. Ergebnisse: Insgesamt wurden 23 interne Dokumente analysiert. Am häufigsten fanden sich Textstellen zuSchutzmaßnahmen, Material sowie Screening. Das Thema MRE bei Patienten am Lebensende fand kaum Erwähnung. Schlussfolgerungen: In Dokumenten zur Versorgung von MRE-positiven Patienten liegt der Fokus auf allgemeingültigen Verfahrensanweisungen mit vorrangig praktischen Themen wie zur Pflege benötigtes Material bzw. Schutzmaßnahmen gegen MRE. Die Versorgung von Patienten am Lebensende spielt eine untergeordnete Rolle, weshalb dieses Thema zukünftig in Verfahrensanweisungen stärker fokussiert werden sollt
Keywords: Palliativversorgung; multiresistente Erreger; MRSA; klinische Guidelines; Dokumentenanalyse

Multidrug-resistant bacterial microorganisms (MDRO) in end-of-life care: development of recommendations for hospitalized patients using a mixed-methods approach - Heckel, Maria; Stiel, Stephanie; Herbst, Franziska A.; Tiedtke, Johanna; Sturm, Alexander; Adelhardt, Thomas; Bogdan, Christian; Sieber, Cornel; Schöffski, Oliver; Lang, Frieder; Ostgathe, Christoph (Supportive Care in Cancer, 2018)
Purpose Palliative care professionals are frequently confronted with patients colonized or infected with MDRO. One major challenge is how to balance necessary isolation measures and social inclusion as one of the main principles of palliative and end-of-life care. To date, MDRO-specific policies and protocols vary widely between institutions. Aim: provide empirical recommendations on how to deal with hospitalized MDRO patients in end-of-life care.Methods Recommendations were developed based on (i) initial results of face-to-face interviews and focus groups, (ii) impartial experts' comments and consensus on the draft via online survey and (iii) a face-to-face meeting with consortium members to finalize recommendations. Findings of 158 interviews and six focus groups (39 participants) with patients, family caregivers, staff members and institutional stakeholders contributed to the recommendations. The assessments of 17 experts were considered.Results In total, 21 recommendations were approved. The recommended strategy in dealing with MDRO at the end of life allows case-based application of protection and isolation measures. MDRO diagnostics and therapy involve screening at admission. The recommendations suggest consideration of required accommodation facilities, provided material as well as staff and time resources. The recommendations further highlight the importance of providing for strategies enabling the patient's social inclusion and provision of verbal and written information about MDRO for patients and family caregivers, transparent medical documentation, and staff member training.Conclusion The recommendations summarize the perspectives of individuals and groups affected by MDRO at the end of life and provide practical guidance for clinical routine. Further dissemination and implementation requirements are discussed and should contain the evaluation of the knowledge, views, worries, and anxieties of the target groups.
Keywords: Palliative care; Terminal care; Drug resistance; Multiple; Practice guideline; Methicillin-resistant Staphylococcus aureus; Empirical research

Nasal carriage of methicillin-resistant Staphylococcus aureus (MRSA) at a palliative care unit: A prospective single service analysis - Heckel, Maria; Geißdörfer, Walter; Herbst, Franziska A.; Stiel, Stephanie; Ostgathe, Christoph; Bogdan, Christian (PLoS ONE, 2017)
BACKGROUND: The emergence of multidrug-resistant bacterial microorganisms is a particular challenge for the health care systems. Little is known about the occurrence of methicillin-resistant Staphylococcus aureus (MRSA) and multidrug-resistant Gram-negative bacteria (MDRGNB) in patients of palliative care units (PCU). AIM: The primary aim of this study was to determine the carriage of MRSA among patients of a PCU at a German University Hospital and to assess whether the positive cases would have been detected by a risk-factor-based screening-approach. DESIGN: Between February 2014 and January 2015 patients from our PCU were tested for MRSA carriage within 48 hours following admission irrespective of pre-existing risk factors. In addition, risk factors for MRSA colonization were assessed. Samples from the nostrils and, if applicable, from pre-existing wounds were analysed by standardized culture-based laboratory techniques for the presence of MRSA and of other bacteria and fungi. Results from swabs taken prior to admission were also recorded if available. RESULTS: 297 out of 317 patients (93.7%) fulfilled one or more MRSA screening criteria. Swabs from 299 patients were tested. The detection rate was 2.1% for MRSA. All MRSA cases would have been detected by a risk-factor-based screening-approach. Considering the detected cases and the results from swabs taken prior to admission, 4.1% of the patients (n = 13) were diagnosed with MRSA and 4.1% with MDRGNB (n = 13), including two patients with MRSA and MDRGNB (0.6%). The rate of MRSA carriage in PCU patients (4.1%) was elevated compared to the rate seen in the general cohort of patients admitted to our University Hospital (2.7%). CONCLUSIONS: PCU patients have an increased risk to carry MRSA compared to other hospitalized patients. Although a risk factor-based screening is likely to detect all MRSA carriers amongst PCU patients, we rather recommend a universal screening to avoid the extra effort to identify the few risk factor-negative patients (<7%). As we did not perform a systematic MDRGNB screening, further studies are needed to determine the true prevalence of MDRGNB amongst PCU patients.
EVALuna2:33307

National strategy for palliative care of severely ill and dying people and their relatives in pandemics (PallPan) in Germany-study protocol of a mixed-methods project - Bausewein, Claudia; Hodiamont, Farina; Berges, Natalie; Ullrich, Anneke; Gerlach, C.; Oechsle, Karin; Pauli, B.; Weber, J.; Stiel, Stephanie; Schneider, Nils; Krumm, N.; Rolke, Roman; et al. (BMC Palliative Care, 2022)
Background In the SARS-CoV-2 pandemic, general and specialist Palliative Care (PC) plays an essential role in health care, contributing to symptom control, psycho-social support, and providing support in complex decision making. Numbers of COVID-19 related deaths have recently increased demanding more palliative care input. Also, the pandemic impacts on palliative care for non-COVID-19 patients. Strategies on the care for seriously ill and dying people in pandemic times are lacking. Therefore, the program 'Palliative care in Pandemics' (PallPan) aims to develop and consent a national pandemic plan for the care of seriously ill and dying adults and their informal carers in pandemics including (a) guidance for generalist and specialist palliative care of patients with and without SARS-CoV-2 infections on the micro, meso and macro level, (b) collection and development of information material for an online platform, and (c) identification of variables and research questions on palliative care in pandemics for the national pandemic cohort network (NAPKON). Methods Mixed-methods project including ten work packages conducting (online) surveys and qualitative interviews to explore and describe i) experiences and burden of patients (with/without SARS-CoV-2 infection) and their relatives, ii) experiences, challenges and potential solutions of health care professionals, stakeholders and decision makers during the SARS-CoV-2 pandemic. The work package results inform the development of a consensus-based guidance. In addition, best practice examples and relevant literature will be collected and variables for data collection identified. Discussion For a future "pandemic preparedness" national and international recommendations and concepts for the care of severely ill and dying people are necessary considering both generalist and specialist palliative care in the home care and inpatient setting.
CRIS-Team WoS Importer:2022-01-21

Neue Technologien in Forschung und Palliativversorgung – Die Wissenschaftlichen Arbeitstage der DGP 2024 - Öhl, Natalie; Tewes, Mitra; Stanze, Henrikje; Banse, Christian; Heckel, Maria (Zeitschrift für Palliativmedizin, 2025)
Zusammenfassung Ziel der Studie In der Palliativversorgung und -forschung gewinnen neue Technologien an Bedeutung. Um dieser Entwicklung Rechnung zu tragen, widmeten sich die Wissenschaftlichen Arbeitstage (WAT) 2024 der Deutschen Gesellschaft für Palliativmedizin diesem Thema. Methodik Unter den Teilnehmenden wurden zwei Online-Befragungen durchgeführt: eine vor Durchführung der WAT und eine weitere nach Durchführung der WAT im Rahmen deren Evaluation. Dabei wurden die Technikaffinität und Einschätzungen zu neuen Technologien der Teilnehmenden erhoben. Die Daten wurden mit deskriptiver quantitativer Statistik sowie qualitativer Inhaltsanalyse ausgewertet. Ergebnisse Die Mehrheit der (n=76/80) Teilnehmenden vor den WAT hatte bisher wenig Kontakt mit neuen Technologien (57,9%), 36,8% besaßen Vorerfahrungen. Im Fragebogen zur interaktionsbezogenen Technikaffinität (ATI) hatten 70 Teilnehmende im Mittel einen Score von 3,78 (SD 0,36). Die Potenziale wurden für die Forschung höher eingeschätzt als für die Versorgung, die Risiken für beide Bereiche eher gering bis mittel. Die (n=38/80) Teilnehmenden an der Befragung nach den WAT gaben überwiegend an, nach der Veranstaltung mehr Potenziale neuer Technologien in der Palliativversorgung zu sehen. Schlussfolgerung Die WAT trugen dazu bei, die Wissenschaftler:innen für Potenziale und Risiken neuer Technologien zu sensibilisieren. Abstract Objective New technologies are becoming increasingly important in palliative care and research. To address this development, the Scientific Workdays (WAT) 2024 of the German Society for Palliative Medicine focused on this topic. Methods Two online surveys were conducted among participants: one before the WAT and another as part of the WATʼs evaluation after the event. The surveys aimed to gather information about participantsʼ affinity for technology and their assessments of new technologies. The data were analyzed using descriptive quantitative statistics and qualitative content analysis. Results The majority of participants (n=76/80) prior to the WAT had little prior contact with new technologies (57.9%), while 36.8% had some prior experience. In the questionnaire measuring affinity for technology interaction (ATI), 70 participants had an average ATI score of 3.78 (SD 0.36). The potentials of new technologies were rated higher for research than for care practice, and the risks for both areas were perceived as low to moderate. Participants in the follow-up survey after the WAT (n=38/80) indicated that they predominantly saw greater potential for new technologies in palliative care after attending the event. Conclusion The WAT helped to raise awareness among researchers about the potentials and risks of new technologie
Keywords: Digitalisierung - Technikaffinität - Nachwuchswissenschaftler digitalization - technology affinity - young scientists

Non-kin caregivers of terminally ill people: Contributions, experiences, and needs: A protocol for a mixed-methods study - Heckel, Maria; Herbst, Franziska A. (PLoS ONE, 2024)
Background The role of non-kin caregivers, such as friends, neighbours, and acquaintances, in providing end-of-life care is significant but often overlooked in research and policy discussions. These caregivers provide extensive support for individuals in end-of-life care, in addition to or instead of family members. However, there is limited evidence in the literature regarding the experiences, burdens, and benefits of non-kin caregivers. Aims The aim of this research is to examine the role and contributions of non-kin caregivers in end-of-life care. The study intends to uncover their experiences, associated challenges, benefits, and requirements for support. Methods In order to achieve this objective, a mixed-methods approach will be employed, gathering data through structured questionnaires from approximately 150 non-kin caregivers and in-depth interviews with up to 25 participants. The questionnaires will measure the impact, burden, and benefits of caregiving. The Burden Scale for Family Caregivers, the Benefits of Being a Caregiver Scale, the Family Inventory of Needs, the Positive Mental Health Scale, a Graphic Closeness Scale, and selected items of the Eurofamcare Common Assessment Tool for socio-demographic and caregiving-related data will be used. Quantitative data will be analysed using IBM SPSS Statistics 28 for descriptive analysis and group comparison. The objective of the qualitative in-depth interviews is to obtain a comprehensive picture of the personal experiences, motivations and support needs of members of the non-kin caregivers cohort, who are as heterogeneous as possible in terms of gender, socio-economic status, and facility with the German language. The qualitative data from the interviews will be examined using MAXQDA software, adopting a grounded theory approach for analysis. Discussion This research will develop a comprehensive framework that captures the nuanced experiences of non-kin caregivers at the end of life. The framework will identify areas where support for non-kin caregivers is lacking and where further research is needed. Trial registration The study was prospectively registered in the German Clinical Trials Register (Deutsches Register Klinischer Studien) (Registration No DRKS00033889; date of registration: 05 April 2024). The study is searchable under the International Clinical Trials Registry Platform Search Portal of the World Health Organization, under the German Clinical Trials Register number.
CRIS-Team Scopus Importer:2024-07-12

Öffentliche Wahrnehmung von Palliativversorgung vor, während und nach der COVID-19-Pandemie – eine empirische Untersuchung von Online-Diskursen - Peters, Joachim; Rabenstein, Ulrich; Heckel, Maria; Breindl, Eva; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2024)

Palliative Care and new technologies. The use of smart sensor technologies and its impact on the Total Care principle - Ott, Tabea; Heckel, Maria; Öhl, Natalie; Steigleder, Tobias; Albrecht, Nils; Ostgathe, Christoph; Dabrock, Peter (BMC Palliative Care, 2023)
Background Palliative care is an integral part of health care, which in term has become increasingly technologized in recent decades. Lately, innovative smart sensors combined with artificial intelligence promise better diagnosis and treatment. But to date, it is unclear: how are palliative care concepts and their underlying assumptions about humans challenged by smart sensor technologies (SST) and how can care benefit from SST? Aims The paper aims to identify changes and challenges in palliative care due to the use of SST. In addition, normative guiding criteria for the use of SST are developed. Methods The principle of Total Care used by the European Association for Palliative Care (EAPC) forms the basis for the ethical analysis. Drawing on this, its underlying conceptions of the human and its socio-ethical aspects are examined with a phenomenological focus. In the second step, the advantages, limitations, and socio-ethical challenges of using SST with respect to the Total Care principle are explored. Finally, ethical-normative requirements for the application of SST are derived. Results and Conclusion First, SST are limited in their measurement capabilities. Second, SST have an impact on human agency and autonomy. This concerns both the patient and the caregiver. Third, some aspects of the Total Care principle are likely to be marginalized due to the use of SST. The paper formulates normative requirements for using SST to serve human flourishing. It unfolds three criteria according to which SST must be aligned: (1) evidence and purposefulness, (2) autonomy, and (3) Total Care.
Keywords: Total Care; Smart Sensor Technologies; Artificial Intelligence; Ethics; Quality of life

Palliative care as a digital working world (PALLADiUM) - A mixed-method research protocol - Grimminger, Sandra; Heckel, Maria; Markgraf, Moritz; Peuten, Sarah; Wöhl, Moritz; Gimpel, Henner; Klein, Carsten; Ostgathe, Christoph; Steigleder, Tobias; Schneider, Werner (BMC Palliative Care, 2023)
Background: In Palliative Care, actors from different professional backgrounds work together and exchange case-specific and expert knowledge and information. Since Palliative Care is traditionally distant from digitalization due to its holistically person-centered approach, there is a lack of suitable concepts enabling digitalization regarding multi-professional team processes. Yet, a digitalised information and collaboration environment geared to the requirements of palliative care and the needs of the members of the multi-professional team might facilitate communication and collaboration processes and improve information and knowledge flows. Taking this chance, the presented three-year project, PALLADiUM, aims to improve the effectiveness of Palliative Care teams by jointly sharing available inter-subjective knowledge and orientation-giving as well as action-guiding practical knowledge. Thus, PALLADiUM will explore the potentials and limitations of digitally supported communication and collaboration solutions. Methods: PALLADiUM follows an open and iterative mixed methods approach. First, ethnographic methods – participant observations, interviews, and focus groups – aim to explore knowledge and information flow in investigating Palliative Care units as well as the requirements and barriers to digitalization. Second, to extend this body, the analysis of the historical hospital data provides quantitative insights. Condensing all findings results in a to-be work system. Adhering to the work systems transformation method, a technical prototype including artificial intelligence components will enhance the collaborative teamwork in the Palliative Care unit. Discussion: PALLADiUM aims to deliver decisive new insights into the preconditions, processes, and success factors of the digitalization of a medical working environment as well as communication and collaboration processes in multi-professional teams. Trial registration: The study was registered prospectively at DRKS (Deutsches Register Klinischer Studien) Registration-ID: DRKS0025356 Date of registration: 03.06.21.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Communication; Digital technology; Multi-professional; Palliative care; Terminal care

Palliative Care Patients' Quality of Dying and Circumstances of Death-Comparison of Informal Caregivers' and Health-Care Professionals' Estimates - Stiel, Stephanie; Heckel, Maria; Wendt, Kim Nikola; Weber, Martin; Ostgathe, Christoph (American Journal of Hospice & Palliative Medicine, 2018)
BACKGROUND: Patient-reported outcomes are usually considered to be the gold standard assessment. However, for the assessment of quality of dying and death, ratings of informal caregivers (ICGs) or health-care professionals (HCPs) must be considered for ethical and methodological reasons. This article aims to present results of ICGs' and HCPs' estimates of the questionnaire, quality of dying and death (QoDD) on patients who died in PCUs and to compare the level of agreement of both ratings/raters. METHODS: The parent validation study to this analysis assessed the ICG and HCP versions of the QoDD. Descriptive statistics are presented for each item in both versions. T tests for the estimation of differences between ICG and HCP were performed. Case-related absolute differences between estimates were analyzed regarding the extent of agreement and deviation. RESULTS: Two hundred fifteen matched ICG and HCP ratings were analyzed. The ratings in all 6 QoDD dimensions were high; single items scored low. Mean absolute difference between both ratings was 0.33 (standard deviation [SD]: 3.08; median 0.05) on a 0 to 10 numerical rating scale and ranges between -8.24 (higher rating of ICGs compared to HCPs) and 9.33 (higher rating of HCPs compared to ICGs). CONCLUSIONS: The findings appear to show a high satisfaction with quality of dying and death as rated by ICGs and HCPs, but we suspect this might be indicative of a methodological challenge, that is, a ceiling effect in both assessments. Single low scoring items may provide important clues for improvement in end-of-life care. Although descriptive data show comparable mean values and standard deviations, the actual congruence of ratings is low. In summary, replacing one rating by another cannot be recommended.
EVALuna2:33773

Palliativversorgung in Zeiten der COVID-19-Pandemie: Wandelt sich die öffentliche Wahrnehmung? (Abstract) - Peters, Joachim; Rabenstein, Ulrich; Heckel, Maria; Breindl, Eva; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2022)

PaM - Development and Validation of a palliative medical Integration Model for Melanoma - Bender-Säbelkampf, Sophia; Heckel, Maria; Ostgathe, Christoph; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Partizipation in der Palliativforschung - Heckel, Maria; Gehrmann, Jan; Burggraf, Larissa; Stark, Stefanie; Ullrich, Anneke (Pflege Zeitschrift, 2022)
Partizipation gewinnt im Gesundheitswesen an Bedeutung. Inwiefern und zu welchen Fragen findet Partizipation in der Palliativforschung statt? Eine Online-Befragung von Forschungseinrichtungen (März bis Juni 2022) zeigt, dass in acht von zehn Einrichtungen Fachpersonal, Angehörige sowie Patient*innenvertreter*innen, teils sporadisch, teils regelmäßig, partizipieren - mitbestimmend, mitwirkend und beratend, etwa bei Themen wie Versorgungsstrukturen und -formen. Evaluationen zur erwarteten Qualitätsverbesserung und erleichterten Verbreitung von Forschungsergebnissen fehlen. Partizipation findet ohne Einfluss auf die Themen- und Methodenwahl statt, was aber für die Versorgungspraxis gewinnbringend und durch die Einrichtung permanenter Partizipationsgruppen umsetzbar wäre. Fachbereichsübergreifende Erforschung von Partizipationsformaten lässt konzeptionelle und ressourcenbezogene Vorteile erwarte

Patient*innen gestalten Forschung in der Palliativmedizin mit - Heckel, Maria; Meesters, Sophie; Schildmann, Eva; Ostgathe, Christoph (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2020)
Background: Patient and public participation in health research is of increasing social importance. The participation of citizens (patients, their next or interested parties) is not yet structurally anchored in Germany. This manuscript aims to present and to discuss first experiences with patient and public involvement in two palliative care centers. Methods: In two centers, a general patient and public involvement committee (Erlangen) and a project-associated patient and public involvement group (Munich) were founded. Strategies for recruitment of potential members (public lectures, personal contact, information on the website, leaflets) were developed and applied. Sociodemographic data and motivations were assessed using survey and personal communication. 18 months after foundation citizens were asked to give feedback on participation during personal meetings. Results: The 20 members of the PPI committee (14 female) are between 52 and 86 years old in Erlangen. The PPI group in Munich has 7 members (5 female). Motivations to contribute are, for example, gratefulness for the care of a relative or the wish to share occupational competencies for a good purpose. Voluntary participation took place by consulting the research teams. Consultation was, among others, performed in joint sessions with brainstorming, moderated group discussions, piloting and commenting interview guides, texts or website content. Participation improved the quality of study material and data assessment instruments. Citizens appreciated that they were able to gain new information and meet people from different fields. They partly wished there was a more detailed preparation and debriefing after joint meetings. The research teams did not quantify the considerable staff and time expenses. Discussion: The recruitment strategies used have proved successful, and the experiences so far indicate a positive impact of PPI on research in the field of palliative care. Research is needed to evaluate the resources required and the effect of PPI in palliative care. On a structural level, discussion of PPI as one specification of voluntary engagement in palliative care, centralized provision of general information on PPI in palliative care and the possibilities of exchange between PPI groups and researchers of different facilities, should take place. Conclusion: There is a need for networking and exchange among researchers and citizens of different project groups with experience in PPI. An institutionalized provision of expertise would pave the way for PPI in palliative research.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Palliative care; Participation; Patient and public involvement; Research

Patients and the Public are doing Research in Palliative Medicine - Heckel, Maria; Merkel, Gabriele; Orth, Karlheinz; Schumann, Birgit; Schildmann, Eva; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2019)
CRIS-Team WoS Importer:2019-11-15

Patients' views on the impact of multi-drug-resistant bacterial microorganisms (MDRO) in end-of-life care - A qualitative study using principles of Grounded Theory. - Sturm, Alexander; Ostgathe, Christoph; Stiel, Stephanie; Heckel, Maria; Herbst, Franziska A.; Adelhardt, Thomas; Schöffski, Oliver; Bogdan, Christian; Tiedtke, Johanna; Lang, Frieder; Sieber, Cornel (SPRINGER, 2018)

Perspectives on multidrug-resistant organisms at the end of life - A focus group study of staff members and institutional stakeholders - Herbst, Franziska A.; Heckel, Maria; Tiedtke, Johanna; Adelhardt, Thomas; Sturm, Alexander; Stiel, Stephanie; Ostgathe, Christoph (Zeitschrift für Gerontologie und Geriatrie, 2018)

Perspectives on multidrug-resistant organisms at the end of life: A focus group study of staff members and institutional stakeholders - Herbst, Franziska A.; Heckel, Maria; Tiedtke, Johanna; Adelhardt, Thomas; Sturm, Alexander; Stiel, Stephanie; Ostgathe, Christoph (Zeitschrift für Gerontologie und Geriatrie, 2019)
Background: There is a lack of research into how hospital staff and institutional stakeholders (i. e. institutional representatives from public health authorities, hospital hygiene, and the departments of microbiology, palliative care, and geriatrics) engage with patients who are carriers of multidrug-resistant organisms and receiving end-of-life care. Knowledge of their experiences, workload, and needs should be considered in dealing with hospitalized carriers of multidrug-resistant organisms as well as staff education. Objective: This study explored and compared staff members’ and stakeholders’ perspectives on multidrug-resistant organisms and on provision of end-of-life care to carrier patients. Methods: In this study four focus groups consisting of hospital staff members and institutional stakeholders were formed within a mixed-methods parent study in a palliative care unit at a university clinic and a geriatric ward of a Catholic and academic teaching hospital. Participants discussed results from staff and stakeholder interviews from a former study phase. Data were analyzed according to Grounded Theory and perspectives of staff members and institutional stakeholders were compared and contrasted. Results: Key issues debated by staff members (N = 19) and institutional stakeholders (N = 10) were 1) the additional workload, 2) reasons for uncertainty about handling carrier patients, 3) the format of continuing education, and 4) the preferred management approach for dealing with multidrug-resistant organism carrier patients. Although similar barriers (e. g. colleagues’ ambiguous opinions) were identified, both groups drew different conclusions concerning the management of these barriers. While institutional stakeholders recommended making decisions on hygiene measures under consideration of the specific patient situation, staff members preferred the use of standardized hygiene measures which should be applied uniformly to all patients. Discussion: Staff members and institutional stakeholders perceived similar barriers to practice caused by multidrug-resistant organisms and similar needs for continuing education. The staff members’ preferred management approach might originate from an uncertainty about the multidrug-resistant organism infection risk. Experiences and visions of both groups should be included in a specific recommendation for end-of-life care to ensure behavioral confidence.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Methicillin-resistant Staphylococcus aureus; Multidrug-resistant gram-negative bacteria; Multidrug-resistant organisms; Palliative care; Qualitative research

Physicians' Opinion and Practice With the Continuous Use of Sedatives in the Last Days of Life - Heijltjes, Madelon T.; Morita, Tatsuya; Mori, Masanori; Heckel, Maria; Klein, Carsten; Stiel, Stephanie; Miccinesi, Guido; Deliens, Luc; Robijn, Lenzo; Stone, Patrick; Sykes, Nigel; Hui, David; et al. (Journal of Pain and Symptom Management, 2021)
Context: There are few international studies about the continuous use of sedatives (CUS) in the last days of life. Objectives: We aim to describe the experiences and opinions regarding CUS of physicians caring for terminally ill patients in seven countries. Methods: Questionnaire study about practices and experiences with CUS in the last days of life among physicians caring for terminally ill patients in Belgium (n = 175), Germany (n = 546), Italy (n = 214), Japan (n = 513), the Netherlands (n = 829), United Kingdom (n = 114) and Singapore (n = 21). Results: The overall response rate was 22%. Of the respondents, 88-99% reported that they had clinical experience of CUS in the last 12 months. More than 90% of respondents indicated that they mostly used midazolam for sedation. The use of sedatives to relieve suffering in the last days of life was considered acceptable in cases of physical suffering (87%–99%). This percentage was lower but still substantial in cases of psycho-existential suffering in the absence of physical symptoms (45%–88%). These percentages were lower when the prognosis was at least several weeks (22%–66% for physical suffering and 5%–42% for psycho-existential suffering). Of the respondents, 10% or less agreed with the statement that CUS is unnecessary because suffering can be alleviated with other measures. A substantial proportion (41%–95%) agreed with the statement that a competent patient with severe suffering has the right to demand the use of sedatives in the last days of life. Conclusion: Many respondents in our study considered CUS acceptable for the relief of physical and psycho-existential suffering in the last days of life. The acceptability was lower regarding CUS for psycho-existential suffering and regarding CUS for patients with a longer life expectancy.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Continuous use of sedatives; Deep sedation; End of life care; Palliative care; Palliative sedation; Questionnaire study

Possible age-related differences in healthcare professionals’ perspectives on younger and older patients’ autonomy and decision-making in the context of sedation in specialised palliative care: exploratory secondary qualitative content and linguistic conversation analysis of interviews with healthcare professionals - Kurkowski, Sandra; Heckel, Maria; Pfaller, Larissa; Peters, Joachim; Jeremias, Bazata; Eva, Schildmann; Ostgathe, Christoph (BMC Palliative Care, 2022)
Background Chronic illnesses and multi-morbidity can threaten competence and independence, particularly in old age. Autonomy becomes increasingly important in the context of sedation, as in this case medication leads to (further) changes of consciousness. The study aimed to identify possible age-related differences in the perspectives of healthcare professionals on patients’ autonomy, in the context of sedation in specialised palliative care. Method Secondary analysis of interviews with healthcare professionals, analysed by qualitative content and linguistic conversation analysis. The interviews analysed span 51 healthcare professionals in specialised palliative care across 17 centres (adult inpatient and specialist palliative home care services) in Germany. Results The study shows that the perspectives of healthcare professionals on patients’ autonomy differs according to the age of the patient in the context of sedation in specialised palliative care. The different perspectives may lead to different ways of treating the patients, for example a greater space of autonomy and decision-making for younger patients. Conclusion In particular, measures that may restrict consciousness (e.g. sedation) and thus influence patients’ ability to fully exercise their autonomy and fully participate in decision-making require special attention by healthcare professionals with respect to possible influences on treatment, such as different perceptions by healthcare professionals based on the patient’s age or age-related stereotype
Keywords: End of life care; Palliative care; Age; Ageing; Autonomy; Qualitative content analysis; Linguistic conversation analysis

Präsentation von Palliativstationen und SAPV-Teams im Internet - eine korpusbasierte Metaanalyse von Webseiten - Peters, Joachim; Dykes, Nathan; Heckel, Maria; Ostgathe, Christoph; Habermann, Mechthild (Zeitschrift für Palliativmedizin, 2022)

Scoping Reviews in Palliative Research - Heckel, Maria; Berendt, Julia; Gahr, Susanne; Kauzner, Saskia; Schleef, Tanja; Herbst, Franziska A. (Zeitschrift für Palliativmedizin, 2022)
CRIS-Team WoS Importer:2022-12-16

Screening for Palliative Care Needs: Pilot Data From German Comprehensive Cancer Centers - Roch, Carmen; Heckel, Maria; Van Oorschot, Birgitt; Alt-Epping, Bernd; Tewes, Mitra (JCO Oncology Practice, 2021)
PURPOSE: Guidelines recommend several screening tools to identify patients with complex palliative needs. This diversity and lack of structural recommendations offer a wide scope for implementing screening. Against this background, the current status of implementation at German Comprehensive Cancer Centers (CCCs) funded by the German Cancer Aid has not yet been investigated. METHODS: e-mail survey of the 17 hospital sites of the 13 CCCs. The questionnaire asked for structural characteristics of the centers as well as preconditions of the screening process. Structurally established screening procedures (one item) and standardized workflows, modes of performance, screening tools (four items), modes of training how to screen, and responsibilities (two items) were assessed. RESULTS: In a 2-month period, 15 hospital sites responded; seven hospital sites conducted a palliative care needs (PCN) screening. Only one hospital site carried out PCN screening in almost all oncology departments, but only with the distress thermometer. Other hospital sites determined palliative needs by assessing physical symptoms using the Integrated Palliative Care Outcome Scale or the Minimal Documentation System, and two hospital sites combined tools to determine both physical and psychological stress. The type of screening varied from paper-pencil-based to tablet computer-based documentation. The main barriers to implementation were identified as a lack of human resources and a lack of structural conditions. CONCLUSION: There is a lack of consensus among palliative care specialists and oncologists in the CCCs supported by the German Cancer Aid in PCN screening as well as of structured guidelines and the professional association. Structural requirements should be adapted to these needs, which include both technical and human resources. A combined psycho-oncologic and palliative care screening might help to formulate best practice recommendations.
CRIS-Team WoS Importer:2021-11-05

Social Implications of Technology Applications in Palliative Care - Development of a Conceptual Framework - Öhl, Natalie; Ostgathe, Christoph; Steigleder, Tobias; Klinger, Isabell; Weisser, Alina; Heckel, Maria (World Congress of the European Association for Palliative Care, 2023)

SOP - Management of multiresistent Pathogens in the Palliative Care Unit - Ostgathe, Christoph; Stachura, Peter; Heckel, Maria; Brunner, Sarah; Gahr, Susanne; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Foertsch, Baerbel; Klein, Carsten (Die Onkologie, 2022)
Infobox 1 SOP aus der Reihe „SOPs zur palliativen Versorgung von Patienten im Netzwerk der deutschen Comprehensive Cancer Center“, erstellt von der AG Palliativmedizin der von der Deutschen Krebshilfe geförderten Comprehensive Cancer Center (CCC
CRIS-Team WoS Importer:2022-10-07

SOP – Mitbetreuung der Angehörigen von Patient:innen mit einer nicht heilbaren Krebserkrankung in der Sterbephase - Oechsle, Karin; Berendt, Julia; Gebert, Tanja; Heckel, Maria; Hentschel, Leopold; Hornemann, Beate; Jentschke, Elisabeth; Neukirchen, Martin; van Oorschot, Birgitt; Rechenmacher, Michael; Schnabel, Astrid; Simon, Steffen; et al. (Die Onkologie, 2024)
CRIS-Team Scopus Importer:2024-10-25

Soziale Implikationen von Gesundheitstechnologien in der Palliativversorgung – Entwicklung eines konzeptionellen Rahmenwerks - Öhl, Natalie; Steigleder, Tobias; Hille, Eva Maria; Braun, Markus; Weisser, Alina; Muehlensiepen, Felix; Vossiek, Martin; Eskofier, Björn; Kölpin, Alexander; Forbes, C C; Ostgathe, Christoph; Heckel, Maria (Zeitschrift für Palliativmedizin, 2024)
Hintergrund Neue Gesundheitstechnologien wie beispielsweise Apps, radarbasierte Messtechniken oder Robotik bieten Potentiale zur Unterstützung der Palliativversorgung. Ihr Einsatz führt zu sozialen Auswirkungen in der Versorgungspraxis, die vielschichtig, teils verzögert erkennbar und zu berücksichtigen sind. Da soziale Teilhabe und zwischenmenschliche Begegnungen in der Palliativversorgung zentrale therapeutische Konzepte ausmachen ist hier besondere Vorsicht geboten. Gesundheitstechnologien dürfen die Grundsätze der Palliativversorgung nicht stören oder beeinträchtigen. Um dies sicherzustellen sind die sozialen Auswirkungen von Gesundheitstechnologien bei deren Entwicklung und Nutzung fortlaufend zu analysieren und zu berücksichtigen. Bislang fehlt eine Konzeptionalisierung sozialer Implikationen von Gesundheitstechnologien in der Palliativversorgung. Methode Zur Erforschung sozialer Implikationen von Gesundheitstechnologien in der Palliativversorgung wurde zwischen September 2022 und Juli 2023 ein sequentielles Forschungsdesign mit Methoden der qualitativ-empirischen Sozialforschung angewandt: (1) Zunächst wurden iterative interdisziplinäre Diskussionsrunden durchgeführt und mittels konzeptioneller Mapping-Methode ausgewertet. Darauf aufbauend folgten (2) drei Fokusgruppen mit Forschenden, medizinischem Personal und einer Patient-and-Public-Involvement Gruppe, welche mittels qualitativ strukturierter Inhaltsanalyse ausgewertet wurden. Mit den Ergebnissen wurde ein Rahmenwerk – das CARE-HAUS Rahmenwerk – entwickelt, dessen Anwendbarkeit in zwei Fallstudien (3) beispielhaft anhand von radarbasierten Messtechniken und Wearables zur Bewegungsüberwachung überprüft wurde. Das Forschungsdesign wurde von fortlaufenden iterativen narrativen Literaturrecherchen begleitet. Ergebnisse Das CARE-HAUS Rahmenwerk konzeptualisiert soziale Implikationen von Gesundheitstechnologien in der Palliativversorgung. Es zeigt Bereiche auf, in denen Gesundheitstechnologien förderliche und potenziell hinderliche Auswirkungen auf die Versorgungspraxis haben können, wobei die Grundsätze und Zielsetzungen der Palliativversorgung als Maßstab gelten. Die identifizierten Bereiche umfassen die beteiligten Akteur:innen und ihre Charakteristika, Interaktionen, Rollen, Aufgaben und Prozesse im Versorgungskontext und schließlich gesellschaftliche, strukturelle, organisatorische und fachliche Rahmenbedingungen. Schlussfolgerung Das CARE-HAUS Rahmenwerk bietet eine Orientierung für die Analyse sozialer Implikationen vor und während Technologieentwicklungen und -implementierungen. Künftig muss die Anwendbarkeit des CARE-HAUS Rahmenwerks in weiteren Studien evaluiert werde

Sprache in Bewegung – Schlüsselbegriffe der Palliativmedizin im Wandel der Zeit - Peters, Joachim; Heckel, Maria; Ostgathe, Christoph; Habermann, Mechthild (Zeitschrift für Palliativmedizin, 2019)

Staff members' ambivalence on caring for patients with multidrug-resistant bacteria at their end of life: A qualitative study - Tiedtke, Johanna; Stiel, Stephanie; Heckel, Maria; Herbst, Franziska A.; Sturm, Alexander; Sieber, Cornel; Ostgathe, Christoph; Lang, Frieder (Journal of Clinical Nursing, 2018)
Aims and objectivesTo explore healthcare professionals' personal experiences, feelings and attitudes about caring for hospitalised patients with multidrug-resistant bacteria in palliative and geriatric care.BackgroundWorking in end-of-life care involves at times burdening demands that affect not only healthcare professionals personally but also their actions. It is suggested that multidrug-resistant bacteria and their consequences for colonised or infected patients in hospitals are among the challenges for all professionals in end-of-life care. Little is known about the feelings and experiences of staff members during healthcare activities with regard to these bacteria.DesignA qualitative interview study in two German hospitals.MethodsWe interviewed 35 staff members from a German palliative care unit and a geriatric unit about their experiences with multidrug-resistant bacteria in end-of-life care and the management of colonised or infected patients. Semistructured interviews were transcribed verbatim and analysed using grounded theory.ResultsInterviewees represented two interdisciplinary teams with 40% nurses, 26% physicians and 34% other professionals. Salient themes that were identified included impact of multidrug-resistant bacteria on staff members' personal actions, feelings and attitudes towards the bacteria and the required isolation measures. Besides higher workload and consequences for working routines, the patients' palliative care needs were recognised, as well as the necessary protection measures to avoid contaminations in hospital. Healthcare professionals reported a dilemma that they experienced when facing these diverse demands.ConclusionsFindings point to emotional and behavioural ambivalence in end-of-life care among staff members because necessary isolation measures and particular situation in end-of-life care create unsolvable conflicts for healthcare professionals. Possible strategies to cope with ambivalence are discussed.Relevance to clinical practiceHealthcare professionals in palliative and geriatric care have to deal with multidrug-resistant bacteria and have to face contradictory feelings while trying to fulfil patients' needs as well as isolation requirements.
Keywords: dual-process model; end-of-life care; geriatric care; interdisciplinary teams; multidrug-resistant bacteria; palliative care; protective measures; qualitative research

Standard Operating Procedures (SOPs) for Palliative Care in German Comprehensive Cancer Centers - An evaluation of the implementation status - Lödel, Sarah; Ostgathe, Christoph; Heckel, Maria; Oechsle, Karin; Gahr, Susanne (BMC Palliative Care, 2020)
Background: The working group for palliative medicine within the Comprehensive Cancer Center (CCC) network funded by the German Cancer Aid in Germany has developed and published 14 Standard Operating Procedures (SOPs) for palliative care in CCCs. This study analyzed to what extent these SOPs have been implemented in the clinical routine in the CCC network one year after their publication. Methods: An online-based survey on the implementation status, limitations in daily practice and further themes was conducted between April and July 2018. In total, 125 health professionals in specialized palliative care from all 16 CCC locations were invited to participate. The data were analyzed descriptively using SPSS. Results: The response rate was 52.8%. More than half of the respondents (57.6%) knew about the free availability of SOPs on the CCC network website. The extent to which each SOP was being used actively in practice by the survey respondents ranged from a low of 22.7% (for the "Fatigue" SOP) to a highest of 48.5% (for the "Palliative Sedation" and "Respiratory Distress" SOPs). The respondents became aware of the SOP through recommendations from colleagues, team meetings or from the head of the department. The SOPs "Respiratory distress of an adult palliative patient" and "Palliative sedation" were perceived as the most practically oriented and understandable. Barriers to use SOPs were mainly limited time resources and lack of knowledge of existence and availability. Conclusions: In practice, better knowledge about the SOPs and at the same time increased use can be achieved through systematic training or discussion of SOPs in regular team meetings. There is a need to take measures to optimize the implementation in clinical practice.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Comprehensive Cancer Center (CCC); Implementation status; Palliative Care; Standard Operating Procedure (SOP); Survey; Symptoms

Sterbewünsche im Kontext stationärer Altenpflegeeinrichtungen – Belastungen und Bedürfnisse von Pflegenden sowie Aspekte für eine einrichtungsinterne Diskussion und Positionsfindung - Jentschke, Elisabeth; Rabe, Antonia; Armbrecht, Helena; Lang, Frieder; Heckel, Maria (Zeitschrift für Palliativmedizin, 2024)
Hintergrund Pflegende in der stationären Altenhilfe werden aufgrund ihrer engen Interaktion mit den Sterbewünschen der pflegebedürftigen Personen konfrontiert, welche den Wunsch nach dem assistierten Suizid umfassen können. Die geschäftsmäßige Förderung der Selbsttötung ist seit der Nichtigkeitserklärung von §217 StGB in Deutschland nicht mehr untersagt. Wenige Studien untersuchen bisher die Belastungen und Unterstützungsbedürfnisse von Pflegenden. Des Weiteren fehlen Anhaltspunkte entlang derer einrichtungsinterne Positionen zu diesem Themenkomplex erarbeitet werden können. Ziele Erfassung von Belastungen und Bedürfnissen der Pflegenden in der stationären Altenpflege am Beispiel der Diakonie im Zusammenhang mit Sterbewünschen und dem assistierten Suizid sowie Identifikation relevanter Aspekte für eine einrichtungsinterne Positionierung. Methode Befragung von Pflegenden mittels eines selbstentwickelten, nicht-validierten Fragebogens. Anschließende Durchführung von semistrukturierten Interviews mit im Pflegekontext ausgewiesenen Fachpersonen zu ausgewählten Fragebogenergebnissen und Praxislösungen zum Umgang mit Sterbewünschen und dem assistierten Suizid in der stationären Altenhilfe. Die Daten wurden deskriptiv sowie mit der fokussierten Inhaltsanalyse nach Kuckartz analysiert. Ergebnisse Die Daten von 434 Pflegenden und 8 Fachpersonen wurden ausgewertet. 98% (n=423) der Pflegenden gaben in der Befragung an, Erfahrungen mit der Äußerung von Sterbewünschen gemacht zu haben, während 93% (n=403) verneinten, dass es in ihrer Einrichtung schon einmal einen assistierten Suizid gegeben habe. Zudem wünschten sich zwei Drittel (n=299) der Befragten im Umgang mit Sterbewünschen und Wünschen nach dem assistierten Suizid Unterstützung durch Supervision, Fortbildungen und klare Handlungsanweisungen. Aus den Interviews mit fachlich erfahrenen Personen (n=8) ließen sich eine angemessene Qualifizierung der Pflegenden, das Vorhandensein eines Netzwerks, die Teamkultur sowie die zeitlichen Ressourcen als relevante Faktoren erkennen, anhand derer die Positionen verschiedener Interessengruppen zum Umgang mit dem assistierten Suizid beschrieben werden können. Schlussfolgerung Der Umgang mit Sterbewünschen und Wünschen nach dem assistierten Suizid ist für Pflegende der stationären Altenhilfe von praktischer Relevanz. Die Generalisierbarkeit der Ergebnisse ist aufgrund des diakonischen Kontextes beschränkt und ist für andere Settings zu prüfen. Auf Basis der Studienergebnisse wurde von 3 Fachverbänden der Diakonie Bayern eine Arbeitshilfe zur Unterstützung einer gemeinschaftlichen einrichtungsinternen Positionierung für alle Mitarbeitenden erstell
Keywords: Sterbewünsche; assistierter Suizid; Handreichung; stationäre Altenpflege; Pflegende

Support for and involvement of family caregivers in Comprehensive Cancer Center - an Assessment of the Palliative Care Working Group within the network of Comprehensive Cancer Center funded by the German Cancer Aid - Oechsle, Karin; Theissen, Tabea; Heckel, Maria; Schwenzitzki, Lisa; Ullrich, Anneke; Ostgathe, Christoph (Deutsche Medizinische Wochenschrift, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-09-03

Symptom burden and relief in palliative care units of German Comprehensive Cancer Center and other hospitals - Berendt, Julia; Brunner, Sarah; Heckel, Maria; Tewes, Mitra; Ostgathe, Christoph; Gahr, Susanne (Journal of Cancer Research and Clinical Oncology, 2024)
Purpose: The National Hospice and Palliative Registry contains patient data from German hospice and palliative care facilities about symptoms. The aim of the study at hand is to differentiate symptom burden of patients in palliative care units between Comprehensive Cancer Center (CCC) and other hospitals regarding symptom burden and relief of patients in palliative care units. Methods: The registry analysis provided data of patients in palliative care units (2014–2018). We analyzed characteristic and symptom-related data on 18 symptoms, with considerable symptom-burdened patients (moderate or severe). We followed a cancer (yes/no) and facility-specific descriptive analysis (f, %, μ, Mdn, SD, V, r) using SPSS. Results: We evaluated 10,447 patient records (CCC: 4234 pts/non CCC 6,213 pts), 82% with a cancer diagnosis. For cancer patients, the mean age in CCC-affiliated palliative care units was 68 (SD 19–99) years, in others 73 (SD 23–104) years (p < 0.05; V = 0.2). The proportion of patients with significant symptom burden is lower in CCC-affiliated than in other palliative care units. The difference between facilities shows a significant weak effect in pain, vomiting and constipation, depressiveness, anxiety, and tension. The proportion of cases which symptom burden could be alleviated is higher in CCC-affiliated palliative care units with significant weak/medium effect in pain, nausea, vomiting, shortness of breath, constipation, wound care problems, depressiveness, anxiety, tension, confusion, and problems in organizing care. Conclusion: We found differences in symptom burden and symptom relief between CCC-affiliated and other palliative care units. CCCs should continue to feel responsible for sharing knowledge about symptom relief, such as through standard operating procedures and education.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Cancer; Palliative care; Registry; Symptom burden; Symptom relief

Theorien und Modelle in der empirischen Palliativforschung - Kremeike, Kerstin; Heckel, Maria; Herbst, Franziska A.; Meesters, Sophie (Zeitschrift für Palliativmedizin, 2025)
Das Ziel des Artikels ist es, die Bedeutung, Chancen und Grenzen der theoretischen Fundierung in der Palliativforschung durch Anwendung von Theorien und Modellen aufzuzeigen. Forschende sollen angeregt werden, Theorien und Modelle zur Strukturierung, Orientierung und Weiterentwicklung der Palliativforschung explizit zu nutzen und zu beschreiben. <br

The palliative care team in the intensive care unit - Ostgathe, Christoph; Klein, Carsten; Heckel, Maria; Hofmann, Sonja; et al. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2012)
The aim of palliative care is to relieve suffering and stabilize or improve quality of life. Prolongation of life and focus on quality of life seem to be at first glance mutually exclusive. However, in daily clinical routine they occasionally do simultaneously occur, when further medical treatment to prolong life is not successful, not appropriate, or simply refused by the patient. In general, basic competencies in palliative care should be offered by the intensive care unit teams. In complex cases, it can be reasonable to integrate a palliative care team (PCT) which can support treatment for those patients with regard to symptom-oriented therapy. They also facilitate referral of seriously ill patients to a hospice or home. Palliative care consultation is recommended, if distressing symptoms can not be alleviated sufficiently or support for referral of terminally ill patients is sought. In addition, a PCT can provide support in discussions about withdrawal of life-prolonging treatments and the aims of therapy. © 2012 Springer-Verlag.
Keywords: Communication; Palliative care; Palliative care team; Quality of life; Therapy

The quality of care of the dying in hospital—next-of-kin perspectives - Heckel, Maria; Vogt, Annika R.; Stiel, Stephanie; Radon, Johannes; Kurkowski, Sandra; Goebel, Swantje; Ostgathe, Christoph; Weber, Martin (Supportive Care in Cancer, 2020)
Purpose: Providing high-quality care for the dying is essential in palliative care. Quality of care can be checked, compared, and improved by assessing responses from bereaved next-of-kin. The objectives of this study are to examine quality of care in the last 2 days of life of hospitalized patients considering specific aspects of their place of care. Methods: The “Care of the Dying Evaluation” (CODE™) questionnaire, validated in German in 2018 (CODE-GER), examines quality of care for the patient and support of next-of-kin, allocating values between 0 (low quality) and 4 (high quality). The total score (0–104) is divided into subscales which indicate support/time given by doctors/nurses, spiritual/emotional support, information/decision-making, environment, information about the dying process, symptoms, and support at the actual time of death/afterwards. Next-of-kin of patients with an expected death in specialized palliative care units and other wards in two university hospitals between April 2016 and March 2017 were included. Results: Most of the 237 analyzed CODE-GER questionnaires were completed by the patient’s spouse (42.6%) or children (40.5%) and 64.1% were female. Patients stayed in hospital for an average of 13.7 days (3–276; SD 21.1). Half of the patients died in a specialized palliative care unit (50.6%). The CODE-GER total score was 85.7 (SD 14.17; 25–104). Subscales were rated significantly better for palliative care units than for other wards. Unsatisfying outcomes were reported in both groups in the subscales for information/decision-making and information about the dying process. Conclusion: The overall quality of care for the dying was rated to be good. Improvements of information about the dying process and decision-making are needed. Trial registration: DRKS00013916
CRIS-Team Scopus Importer:2020-05-22
Keywords: Caregivers; Death; Outcome assessment (healthcare); Palliative care; Quality; Surveys

Understanding institutional stakeholders' perspectives on multidrug-resistant bacterial organism at the end of life: a qualitative study - Heckel, Maria; Herbst, Franziska A.; Adelhardt, Thomas; Tiedtke, Johanna; Sturm, Alexander; Stiel, Stephanie; Ostgathe, Christoph (Clinical Interventions in Aging, 2017)
Information lacks about institutional stakeholders' perspectives on management approaches of multidrug-resistant bacterial organism in end-of-life situations. The term "institutional stakeholder" includes persons in leading positions with responsibility in hospitals' multidrug-resistant bacterial organism management. They have great influence on how strategies on multidrug-resistant bacterial organism management approaches in institutions of the public health system are designed. This study targeted institutional stakeholders' individual perspectives on multidrug-resistant bacterial organism colonization or infection and isolation measures at the end of life.Between March and December 2014, institutional stakeholders of two study centers, a German palliative care unit and a geriatric ward, were queried in semistructured interviews. Interviews were audiotaped, transcribed verbatim, and analyzed qualitatively with the aid of the software MAXQDA for qualitative data analysis using principles of Grounded Theory. In addition, two external stakeholders were interviewed to enrich data.Key issues addressed by institutional stakeholders (N=18) were the relevance of multidrug-resistant bacterial organism in palliative and geriatric care, contradictions between hygiene principles and patients' and family caregivers' needs and divergence from standards, frame conditions, and reflections on standardization of multidrug-resistant bacterial organism end-of-life care procedures. Results show that institutional stakeholders face a dilemma between their responsibility in protecting third persons and ensuring patients' quality of life. Until further empirical evidence establishes a clear multidrug-resistant bacterial organism management approach in end-of-life care, stakeholders suggest a case-based approach.The institutional stakeholders' perspectives and their suggestion of a case-based approach advance the development process of a patient-, family-, staff-, and institutional-centered approach of how to deal with multidrug-resistant bacterial organism-positive patients in end-of-life care. Institutional stakeholders play an important role in the implementation of recommendations following this approach.
EVALuna2:26216

Use of sedative drugs in specialist palliative care (iSedPall): a multi-modal intervention pilot study protocol - Ostgathe, Christoph; Bausewein, Claudia; Schildmann, Eva; Bazata, Jeremias; Heckel, Maria; Kauzner, Saskia; Klein, Carsten; Krauss, Sabine H.; Kremling, Alexander; Schneider, Manuela; Seifert, Andreas; Ziegler, Kerstin; et al. (Pilot and Feasibility Studies, 2025)
Background: The use of sedative drugs in specialist palliative care is common but presents challenges due to specific medical, ethical, and legal considerations. There is little to no assistance for administering adequate sedative drug doses, ensuring accurate documentation before and during sedation, or managing ethically and legally challenging situations. In 2021, the SedPall study group published recommendations on the use of sedative drugs in palliative care. The German Association for Palliative Medicine endorsed the dissemination of the recommendations nationwide. However, disseminating recommendations alone does not necessarily lead to changes in clinical practice. In the project “Development and piloting of a multi-modal intervention for the use of sedative drugs in specialist palliative care (iSedPall)”, we will develop a multi-modal intervention that implements these national recommendations into practical tools for healthcare professionals in specialist inpatient and home care settings. In the pilot study described below, we aim to test the feasibility of the multi-modal intervention, its appropriateness, and acceptability as primary feasibility outcomes of the multi-modal intervention. Additionally, we aim to assess the feasibility of measuring healthcare professionals´ confidence in using sedative drugs as an outcome indicator for a possible subsequent study. Methods and analysis: We will use a mixed-methods approach to develop and pilot a multi-modal intervention. The primary feasibility outcomes and formative evaluation of the implementation process will be explored using quantitative (retrospective cohort study, survey) and qualitative elements (focus groups, interviews). Additionally, we will pilot the measurement of healthcare professionals´ confidence in using sedative drugs as an outcome indicator through a pre-post survey. Four specialist palliative care services will pilot the complex intervention for nine months. Due to the complexity of the intervention, we will follow the principles of the MRC framework for complex interventions and will apply a Theory of Change approach. The intervention will include different elements to be used throughout the patients’ treatment in inpatient and home specialist palliative care considering medical, ethical, and legal aspects for the use of sedative drugs and intentional sedation. The evaluation of the overall feasibility and the decision about proceeding to an implementation study will be based on the integration of quantitative and qualitative data, according to our mixed-methods approach. Discussion: This project is the first attempt to translate national recommendations on best practices for sedative drug use into a multi-modal intervention and tests its feasibility. The study group identified potential risks and challenges related to the intervention´s feasibility, acceptability, and appropriateness in advance. To mitigate these risks, the study protocol is based on a theoretical framework, developed through a Theory of Change approach. Participatory elements and the involvement of different stakeholders are expected to enhance user acceptance and feasibility, potentially improving the development of supporting materials for sedative drug use in specialist palliative care while considering the interests of non-professionals. Trial registration: Registered in the German Clinical Trials Register, DRKS-ID: DRKS00027241; Registered: 10/12/2021; https://www.drks.de/drks_web/setLocale_EN.do.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Multi-modal intervention; Palliative care; Sedative drugs; Study protocol

Validation of the German Version of the Quality of Dying and Death Questionnaire for Health Professionals - Heckel, Maria; Bussmann, Sonja; Stiel, Stephanie; Ostgathe, Christoph; Weber, Martin (American Journal of Hospice & Palliative Medicine, 2016)
To validate the Quality of Dying and Death (QoDD) instrument for health professionals (QoDD-D-MA) and to test its feasibility in 2 German palliative care units (PCUs).The QoDD was translated from English to German and then retranslated following European Organisation for Research and Treatment of Cancer (EORTC) guidelines. Data were collected in 2 German PCUs to calculate aspects of validity and reliability.Mean total score was 83.05 (range 49-100; N = 232). The QoDD-D-MA showed satisfactory psychometric properties, Cronbach ? = .830; interrater reliability r = .245 (P < .01). The QoDD-D-MA was independent of patients' demographic and clinical aspects. Some challenges occurred when applying the instrument.Feasibility could be improved by adapting the QoDD-D-MA to create a self-assessment version and finding a solution for items that result in many missing data. Future research should validate the QoDD-D-MA in other care settings.
EVALuna2:26211

Well connected - optimally cared for! : Beneficial factors of collaboration in hospice and palliative care networks in Bavaria - Herbst, Franziska A.; Heckel, Maria; Stiel, Stephanie; Ostgathe, Christoph (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2017)
The Bavarian State Ministry of Health and Care fosters the establishment of regional hospice and palliative care networks in Bavaria, Germany. Little is known about well-tried structures and beneficial strategies of collaboration within such networks.The present study aims to investigate general conditions under which hospice and palliative care networks in Bavaria perform successfully and to explore modes of working, forms of organisation, and channels of communication.Data were collected between March and June 2015 in semi-structured interviews with ten coordinators and chairpersons of ten Bavarian hospice and palliative care networks. Results of this status quo analysis concerning aspects of network models and beneficial factors of networking were discussed in a subsequent workshop. The workshop took place in November 2015 with eight representatives of five networks. Individual interviews and the discussion of the diagnostic workshop were audiotaped and transcribed verbatim. Data were analysed with the aid of the computer-assisted qualitative data analysis software MAXQDA (Software für qualitative Datenanalyse (1989-2015). VERBI Software Consult Sozialforschung GmbH, Berlin, Germany). Hypotheses were formulated adapted from Grounded Theory.Networking factors and characteristics are quite congruent. Beneficial and diverse factors identified by network coordinators and moderators represent three major topics: network organisation and coordination, communication and information channels, and public visibility.Well-tried and established practices of networking are present in the hospice and palliative care networks included in the study. The experiences and visions of the networks will foster the compilation of a best practice recommendation for the establishment of new and the enhancement of existing networks.
EVALuna2:26202

What Does “Palliative” Mean? Sentiment, Knowledge, and Public Perception Concerning Palliative Care on the Internet since the COVID-19 Pandemic - Peters, Joachim; Heckel, Maria; Breindl, Eva; Ostgathe, Christoph (Palliative Medicine Reports, 2024)

„ Wir sind ‚der Blick von außen‘ mit Beteiligung ‚von innen‘“ - Einbindung eines Patient:innen- und Angehörigenbeirates in Klinik und Forschung - Heckel, Maria (2023)
Wenn Betroffene, etwa in Form von Patient:innen und Angehörigenbeiräten, an Fragen der Qualität klinischer Versorgung beteiligt werden, hat das auch mittelbar Auswirkung auf die Praxis. Ihre Perspektiven und Erfahrungen können beratend und partizipativ in die Palliativforschung eingebunden werden. Dafür eignet sich etwa Forschung zu Therapieverfahren, Entscheidungsprozessen im Versorgungsalltag, Unterstützungsangeboten sowie neue technische Anwendungen. Damit dies gelingen kann, braucht es eine Offenheit für Kritik sowie kreative, neue Formen der Beteiligung, damit auch schwer kranke Patient:innen am Lebensende mitwirken könne
Keywords: Angehörige; Patient:innenbeirat; Angehörigenbeirat; Forschung

Wishes of nursing home residents for their dying - Kurkowski, Sandra; Heckel, Maria; Volland-Schüssel, Käte (Zeitschrift für Gerontologie und Geriatrie, 2018)
BACKGROUND: Institutions of inpatient geriatric care are dependent on specific and practicable concepts for the terminal care of old people, because residential and nursing homes are places for the last phase of life. OBJECTIVE: The objective of this study was to identify the wishes of residents for their dying who live in a residential or nursing home. METHOD: The analysis was based on 10 semi-structured expert interviews with residential and nursing home residents. The interviews were evaluated using the method of qualitative summarizing content analysis. Based on the grounded theory a procedure was selected in which data were collected, prepared and evaluated in parallel. RESULTS AND DISCUSSION: Residents expressed, inter alia, the following wishes: not to receive life-prolonging measures, not to have pain, not to be in need of care or bedridden, to receive affection while dying and to find forgiveness and reconciliation as well as to die peacefully in the residential and/or nursing home. In addition, there were a variety of wishes, which, due to their diversity make a unified approach to the palliative care of older people in residential and/or nursing homes impractical. The study showed that residents are thinking about dying and/or death, have desires for their dying and are also willing to talk about it. The recording and the translation of these wishes and also the response to the residents' fears can be achieved by the implementation of a palliative culture and the training of employees.
EVALuna2:204778